Changing thunderstorms environments in Saudi Arabia: Frequency, variability and drivers of change - Moutassem El Rafei; Andrew Dowdy; Mazen E. Assiri; Md. Arfan Ali; Muhammad Haroon Siddiqui; Sajjad Saeed; Saeed Ahmad Alghamdi; Shamsuddin Shahid (Atmospheric Research, 2026)

Deubiquitinases at the crossroads of ferroptosis and cancer therapy: mechanisms and therapeutic potential - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Sumaya Nadhim Mohammed; Haitham L. Abdulhadi; Manoj A. Vora; Tina Saeed Basunduwah; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Wessam T. Muslem (Molecular Biology Reports, 2026)

Genome-wide identification, in-silico characterization, and expression analysis of polygalacturonases in different fungal species - Laiba Amin; Imran Zafar; Adil Jamal; Syed M. Safeer Mehdi Bokhari; Fayez Saeed Bahwerth; Muhammad Noman (Molecular Genetics and Genomics, 2026)

Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Comparative Analysis of Polymeric and Lipid Polymer Hybrid Nanoparticles: In-Vitro and In-Vivo Analysis for Pulmonary Delivery of Atorvastatin - Kifayat Ullah Shah; Muhammad Usama Ghani Khan; Fahad Y. Sabei; Muhammad Danish Saeed; Firdous Ahmad Burki; Muhammad Yasir Ghani Khan; Awaji Y. Safhi; Ahmad Salawi; Abdullah Alsalhi; Ali Hanbashi (Journal of Pharmaceutical Innovation, 2026)

CRISPR–cas systems in pharmacology: functional pharmacogenomics, drug screening, resistance, and therapeutic translation - Muhammad Saeed Akhtar; Adnan Amin (Functional & Integrative Genomics, 2026)

Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Portable metagenomics for preventive surveillance and outbreak control in livestock and poultry: Pathogen detection, resistome profiling, and antimicrobial stewardship - Muhammad Saeed Akhtar; Wajid Zaman (Research in Veterinary Science, 2026)

Engineering MXene-based platforms for electrocatalytic CO2 and N2 reduction reactions; synthesis, modification strategies, and mechanistic insights - Sami Ur Rahman; Saeed Anwar; Awal Noor; Sadaf Qayyum; Yelubay Madeniyet; Niaz Muhammad (Journal of Environmental Chemical Engineering, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Photocatalytic Degradation of Eosin Yellow Dye by Ti doped NiO Nanoparticles and their Antibacterial Activity - Mazhar Ali; Muhammad Tajdar Jandal; Muhammad Owais; Hamad Ali; Zahid Ali; Khalid Saeed (Water, Air, & Soil Pollution, 2026)

The speed–precision paradox in seeding technology: a system-level review of regime transitions, validation gaps, and energy trade-offs - Saddam Hussain; Zhaoyu Rui; Junyan He; Zhao Zhang; Mustafa Mhamed; Muhammad Faheem; Seyed Mohamad Javidan; Muhammad Usman Farid; Alaa Saeed; Mahmoud A. Abdelhamid (Computers and Electronics in Agriculture, 2026)

Multibiomarker assessment of greenly synthesized silver nanoparticles toxicity in the Tor putitora - Noman Waheed; Adeeba Naseer; Sabahat Saeed; Muhammad Fiaz Khan; Yukun Zhang; Venkata Siva Naga Sai Goli (Marine Pollution Bulletin, 2026)

BrAKT1 overexpression enhances clubroot susceptibility through dysregulation of host physiological processes in pak choi - Samiah Arif; Yǔmeng Yan; Yufan Ge; Muhammad Sanaullah Malik; Ping Li; Saeed ur Rahman; Yidong Zhang (Physiological and Molecular Plant Pathology, 2026)

Integrated evaluation of salt tolerance in cigar tobacco (Nicotiana tabacum L.) varieties for sustainable cultivation in saline environments - Munib Ahmad; Uzair Ullah; Muhammad Ateeq; Shah Zeb Khan; Saeed Ullah; Shaista Jabeen; Maqsood Ul Hassan; Sadam Khan; Pingping Wang; Suiling Ai; Lixin Zhang (Journal of Environmental Management, 2026)

Silver-based N-heterocyclic carbene (NHC) complexes as emerging strategies against antimicrobial resistance - Subhangi Nandi; Muhammad Shehroz Zafar; Ziyad A. Alhussain; Saeed Ahmad; Ghazala Iram; Farhan Ahmad (Archives of Microbiology, 2026)

Retraction Note: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Biochemical analysis and antimicrobial potential of Mastacembelus armatus epidermal mucus - Muhammad Saeed Khan; Shandana Ali; Muhammad Qasim; Farman Ullah Dawar; Waheed Ullah (Journal of Fish Biology, 2026)
The epidermal mucus of fish plays an important role in innate immunity, providing both physical and biochemical protection through a complex matrix of bioactive molecules. The present study explored the biochemical characterization, bactericidal, and fungicidal activities of Mastacembelus armatus (Zig‐Zag eel) epidermal mucus treated with Aeromonas hydrophila . Extracts of epidermal mucus (ethanolic and acidic) of Mastacembelus armatus showed antimicrobial activity against selected resistant bacteria and fungi. The zone of inhibition (ZOI), which was measured in millimetres, revealed differences in activity between different fungi and bacteria. The acidic extract demonstrated noticeably higher ZOI values against various MDR bacteria and fungi was more effective than the ethanolic extract. Strong peaks in the Fourier transform infrared (FTIR) spectrum of Mastacembelus armatus indicated the presence of metabolic components in the epidermal mucus. The O–H and N–H stretching vibrations, which are indicative of water content and protein‐based molecules such as mucins or amide, are shown by a large peak at 3272.60 cm −1 . This result suggests that fish epidermal mucus has the potential to contribute enormously to the defence of fish against bacteria and fungi. Therefore, this study could be evidence in favour of the substitution of chemical antibiotics with fish epidermal mucus as a new ‘antimicrobial’ introduced in aquaculture and in humans against bacterial infections.

Retraction notice to “Responses of microbial communities in rhizocompartments of king grass to phytoremediation of cadmium-contaminated soil” [Sci. Total Environ. 904 (2023) 167226] - Muhammad Khalid; Xinxin Liu; Saeed ur Rahman; Asad Rehman; Chang Zhao; Xiaoxiao Li; Bian Yucheng; Nan Hui (Science of The Total Environment, 2026)

Retraction notice to “Phosphorus elevation erodes ectomycorrhizal community diversity and induces divergence of saprophytic community composition between vegetation types” [Sci. Total Environ. 793 (2021) 148502] - Muhammad Khalid; Baoming Du; Haoxin Tan; Xinxin Liu; Lantian Su; Saeed-ur-Rahman; Mehran Ali; Chunjiang Liu; Ningxiao Sun; Nan Hui (Science of The Total Environment, 2026)

Drosophila Tet mediates the host IMD antibacterial immune defense in a catalytic activity-independent manner - Chuchu Zhang; Muhammad Abdul Rehman Saeed; Yiheng Jin; Erwen Ding; Yajie Su; Sheng Hu; Ruirui Tan; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

Silicon seed inoculation enhances antioxidant defenses, physio-biochemical mechanisms and yield traits in maize hybrids under heat stress conditions at vegetative and tasseling stages - Ijaz Hussain; M. Habib Ur-Rahman; Rao Muhammad Ikram; Muhammad Baqir Hussain; Saeed Ahmad; Reimund P. Roetter (Field Crops Research, 2026)

Green Synthesis of a ZnO@Sorghum Nano-Bioadsorbent for Enhanced Dye Wastewater Treatment - Muhammad Arslan Khalil; Bushra Sadia; Saima Noreen; Faisal Saeed Awan; Azeem Iqbal Khan; Muhammad Asif; Bilal Ahmad (Water, Air, & Soil Pollution, 2026)

Structure Guided Identification of Small Molecule Inhibitors Targeting Staphylococcus aureus α-Hemolysin - Saeed Ullah Khattak; Nida Raza; Mawahib Ahmed; Ayesha Saleem; Muhammad Salim; Sajjad Ahmad (Journal of Pharmaceutical Innovation, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Molecular evidence of two begomoviruses and a novel DNA-B infecting Duranta erecta variegata in Pakistan - Afzal Akram; Mahnoor Jamil; Imran Amin; Jodi A. Scheffler; Brian E. Scheffler; Muhammad Saeed; Shahid Mansoor (Virus Genes, 2026)

Spatiotemporal dynamics of historical and future drought conditions over the Arabian Peninsula from ERA5 and CMIP6 data - Muhammad Haroon Siddiqui; Mazen E Assiri; Sajjad Saeed; Md Arfan Ali; Moutassem El Rafei; Shahad Bahamdan; Abdullah Masoud Alqahtani; Abdulrahman AlHaidari; Abdulrahman Alsalhi; Ohood Alzahrani; Shamsuddin Shahid (Journal of Earth System Science, 2026)

Entomocidal effect of green synthesized titanium dioxide nanoparticles using Aloe vera Extract against Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2026)

Environmental pharmaceutical and antibiotic mixtures: An exposomics-guided framework for mechanistic toxicology - Muhammad Saeed Akhtar; Wajid Zaman (Toxicology Letters, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Nanotechnology driven paradigms for sustainable agriculture: A holistic assessment of efficacy, mechanisms, and environmental footprint - Wajid Saeed; Samavia Mubeen; Sana Basharat; Qiqi Peng; Aliya Ayaz; Enerand Mackon; Muhammad Umer; Furkhanda Kalsoom; Muhammad Waseem; Yun li; Pingwu Liu (European Journal of Agronomy, 2026)

Nanoparticles in wheat (Triticum aestivum L) cultivation: a promising solution to alleviate heavy metal toxicity - Eimaan Aamer; Muhammad Saeed; Samia Muhammad Arif; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2026)

Infectious clone–based dissection of delayed pathogenicity and evolutionary dynamics of Papaya leaf curl Guangdong virus (PaLCuGdV) - Renshu Huang; Muhammad Arif; Amna Saeed; Cheng Song; Omer Beyhan; Muhammed Said Yolcu; Islem Abid (European Journal of Plant Pathology, 2026)
Papaya leaf curl Guangdong virus (PaLCuGdV) is an economically significant begomovirus, although its pathogenicity and evolutionary dynamics are poorly understood. This study involved the construction of a full infectious clone of PaLCuGdV, which was agroinoculated into Nicotiana benthamiana ( N. benthamiana ) to assess the infectivity and symptomatology. The infectious clone elicited typical begomoviral symptoms just at 28 days post-inoculation, signifying delayed pathogenicity. Infection efficiency varied with strain, with successful transmission achieved using Agrobacterium GV301, but not with EHA105 alone. Southern blot analysis confirmed active viral DNA replication solely in diseased plants. Comparative sequencing and recombination analysis identified numerous recombination events among worldwide PaLCuGdV isolates, with the newly defined strain serving as a primary recombinant progenitor. These findings indicate that PaLCuGdV displays delayed symptom expression, strain-specific infectivity, and evolutionary diversity driven by recombination, underscoring the value of infectious clone systems for functional and evolutionary studies of begomoviruses.

Molecular Insights into Zinc Uptake and Accumulation in Wheat (Triticum aestivum L.): From Deficiency Responses to Biofortification Strategies - Muhammad Saeed; Pingfang Yang (Journal of Plant Growth Regulation, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Acetic acid-mediated stabilization of texture and pectin networks during thermal processing of Yam (Dioscorea polystachya): Multi-scale structural and molecular insights - Muhammad Burhan Khan Tareen; Nawal Saeed; Yanzhao Liu; Maqbool Ahamd; Xianqiang Chen; Guoxun Chen; Jie Li; Shoulei Yan (Innovative Food Science & Emerging Technologies, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Thermophoretic heat and mass transfer in magnetohydrodynamic transport of a yeleswarapu fluid driven by metachronal cilia - Muhammad Asif Gondal; Zeeshan Asghar; Muhammad Asif Javed; Muhammad Waris Saeed Khan (Dynamics of Atmospheres and Oceans, 2026)

Maize–Soybean Intercropping and Organic Amendments as Sustainable Farming for Higher Productivity, Carbon Sequestration, and Greenhouse Gas Reduction - Sajad Hussain; Du Yongli; Muhammad Shoaib; Sobia Afzal; Hamideh Ghaffari; Fan Yuanfang; Zhang Deyin; Sana ur Rehman; Amjad Saeed; Yang Xinghong; Anshu Rastogi; Marian Brestic (Precision Agriculture, 2026)

Influence of Planting Depth Combined with ZnSO₄ and FeSO₄ on Yield and Starch Quality of Six Potato Cultivars - Harrem Khalid; Muhammad Shafiq; Muhammad Rizwan Tariq; Zain Mushtaq; Maryam Saeed (Potato Research, 2026)

Correction to: Transcriptomics and Ionomics Reveal Arsenic Transport and Detoxification Pathways in Wheat (Triticum aestivum) Genotypes - Muhammad Saeed; Riffat Naseem Malik; Alex Douglas; Gareth J. Norton (Journal of Plant Growth Regulation, 2026)

Transcriptomics and Ionomics Reveal Arsenic Transport and Detoxification Pathways in Wheat (Triticum aestivum) Genotypes - Muhammad Saeed; Riffat Naseem Malik; Alex Douglas; Gareth J. Norton (Journal of Plant Growth Regulation, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Phosphorus availability modulates OsPTF1 expression in Oryza sativa L. - Muhammad Saeed Ahmad; Zulfiqar Ali; Rizwana Maqbool; Sultan Habibullah Khan (Cereal Research Communications, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Exploring the antimicrobial potential of plant-based bioactive compounds in meat products: advances in mechanistic insights, pathogen inhibition, and shelf-life extension - Farhang Hameed Awlqadr; Mohammed N. Saeed; Ammar B. Altemimi; Syamand Ahmed Qadir; Othman Abdulrahman Mohammed; Tablo H. Salih; Aryan Mahmood Faraj; Muhammad Waqar; Hassan Raza (Critical Reviews in Food Science and Nutrition, 2026)

Amino-triggered micro acidity promotes phosphate release from hydroxyapatite and uranium autunite formation - Yishuo Zhang; Yilin Li; Jingyi Sun; Xingnong Wu; Yan Xin; Zhongkui Zhou; Xinghui Wang; Muhammad Saeed; Guofeng Wang; Lingling Peng; Yibao Liu; Yuhui Liu; et al. (Journal of Hazardous Materials, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Machine learning technique for net ecosystem exchange of carbon dioxide simulation and assessment: a regional analysis of Japanese islands - Artem Gorbarenko; Elizaveta Gorbarenko; Dmitry Mikhailov; Alexander Vlasov; Muhammad Saeed (Stochastic Environmental Research and Risk Assessment, 2026)

Assessment of Protective Role of Different Probiotic Strains against Bacterial and Endotoxin-Induced Sepsis in a Mouse Model - Sabeeka Sajjal; Hasnat Ahmad Bilal; Ambreen Zahra; Ayesha Saeed; Aiman Khan; Muhammad Musa Mubashar; Aisha Khatoon; Muhammad Imran Arshad (Probiotics and Antimicrobial Proteins, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Opioidergic and GABAergic mechanisms underlie the anti-nociceptive effects of adamantane amino thiazole derivatives: synthesis, toxicity evaluation and mechanistic insights using standard pre-clinical models - Urooj Aman; Gowhar Ali; Atteeque Ahmed; Aamer Saeed; Mushtaq Ahmad Mir; Nasreena Bashir; Asma Khurshid; Muhammad Ayaz (Inflammopharmacology, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Synergistic effects of zinc and reduced glutathione application on growth, yield, gas exchange attributes, water relations, and metabolite profiles in Zea mays (L.) plants under water deficit irrigation - Farah Saeed; Qasim Ali; Suliman Mohammed Suliman Alghanem; Abida Kausar; Rashida Perveen; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (South African Journal of Botany, 2026)

Artificial intelligence-driven surrogate modeling for computationally efficient and digitally decarbonized LNG process optimization under varying feed composition - Mahmoud Al-Mughairi; Ahmad Saeed; Ashfaq Ahmad; Muhammad Abdul Qyyum (Journal of Cleaner Production, 2026)

Designing glass materials for renewable-energy production through building integrated photovoltaics (BIPV) −A computational approach - Aqsa Aleem; Uzma Habib; Waqas Salman; Muhammad Tariq Saeed (Energy and Buildings, 2026)

Ferruginol as multifunctional abietane diterpenoid-comprehensive pharmacological evaluation and computational drug discovery insight - Iqra Farzeen; Maryam Batool; Zunaira Jaan; Saira Saeed; Muhammad Muzammil Nazir; Shahla Faisal; Asma Ashraf (Phytochemistry Reviews, 2026)

Performance Investigation of ML Algorithms for Potato Blight Classification: The Role of Hyperparameter Tuning - Sadia Saeed; Hafiz Zia Ur Rehman; Muhammad Ureed Hussain; Muhammad Umer Khan; Muhammad Tallal Saeed (Journal of Crop Health, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Spirulina supplementation and human health: An umbrella review of meta-analysis on randomized controlled trials - Nazila Soufi Amlashi; Fahad Rajab Mahmood; Mirza R. Baig; Tina Saeed Basunduwah; Pareshkumar N. Patel; Gulsara Ruziyeva; Gunjan Singh; Muhammad Shahid Iqbal; Munthar Kadhem; Amirali Ebrahimi (Algal Research, 2026)

Spawning and developmental biology of vulnerable catfish, Wallago attu : Implications for quality seed production and stock replenishment - Saeed Akram Khan; Muhammad Khalil Ahmad Khan; Shahid Sherzada (Journal of Fish Biology, 2026)
Freshwater catfish, Wallago attu , is a popular fish species due to its excellent taste and low quantity of intramuscular bones. Scientific and evidence‐based studies on the embryonic and larval development of this vulnerable fish species are limited. We attempted artificial breeding using Ovaprim, and photographs of the embryological events were taken, revealing each stage of early development. For this, a sequence of microscopic analysis was performed using a trinocular digital microscope. Time‐lapse imaging was also performed to calculate the duration of each developmental stage. The eggs were spherical, and highly adhesive, with a diameter of 1.74 ± 0.11 in T1 and T2, 1.86 ± 0.17 and 1.8 ± 0.16 in T3 and T4, respectively. Hatching occurred at 979.33 ± 5.13, 973 ± 21.07, 981.67 ± 11.93 and 969 ± 7.21 min post‐fertilization (mpf) in T1, T2, T3 and T4, respectively. During embryonic development, the blastodisc appeared at 55.33 ± 4.04 (T1), 54.67 ± 5.13 (T2), 58.33 ± 3.79 (T3) and 58.33 ± 3.51 (T4). First cleavage appeared at 64.33 ± 2.08 (T1), 63.67 ± 5.03 (T2), 68 ± 1 (T3) and 66 ± 4.36 (T4) mpf, resulting in two equal blastomeres. Embryonic body movements started at 652 mpf. Free body embryonic development (ranging from the two‐cell to the pre‐hatching stage) took 810 mpf. Hatching occurred at 979.33 ± 5.13 (T1), 973 ± 21.07 (T2), 981.67 ± 11.93(T3) and 969 ± 7.21(T4) mpf, with average larval lengths of 4.88 ± 0.19 (T1), 5 ± 0.16 (T2), 4.88 ± 0.19 (T3) and 4.88 ± 0.28 (T4) mm. Such information will have significant implications on conservation and sustainable seed production of this species. The findings of this study will contribute to the advancement of W. attu aquaculture by providing valuable insights into quality seed production and stock replenishment.

Metabolic reprogramming of neurons in alzheimer disease: a biochemical perspective - Iqra Farzeen; Maryam Batool; Saira Saeed; Ghanva Mustafa; Munaza Yasmeen; Muhammad Muzammil Nazir; Asma Ashraf (Metabolic Brain Disease, 2026)

Molecular characterization and genetic diversity of cotton whitefly Bemisia tabaci infesting cotton crops - Qamar Saeed; Muhammad Sagheer; Ummad ud din Umar; Muhammad Taimoor Shakeel; Mahmoud Moustafa; Mohammed Al-Shahrani; Uthman Algopishi; Muhammad Naeem; Mahmoud Ahmed Amer (International Journal of Tropical Insect Science, 2026)

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Root traits and rhizosphere responses as emerging bioindicators of microplastic pollution in agricultural soils: A review - Qudsia Saeed; Xiankai Lu; Zia Ur Rahman Farooqi; Abdul Ghafoor; Muhammad Naveed; Nimra Maqsood; Hafiz Abdul Kareem; Adnan Mustafa (Environmental Research, 2026)

Level-crossing processing and deep convolutional neural network for arrhythmia classification in telehealth services - Syed Fawad Hussain; Saeed Mian Qaisar; Muhammad Sherjeel (Physical and Engineering Sciences in Medicine, 2026)

Improving growth and physicobiochemical attributes of rice via PGR-based seed priming: a comparative study of establishment methods - Yousaf Saeed; Muhammad Aurangzaib; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Ghulam Murtaza; Lala Gurbanova; Rashid Iqbal (Cereal Research Communications, 2026)

Exploring Fungal Diversity Through COI Primers: A Nontargeted eDNA Approach - Muhammad Asif Qayyoum; Muhammad Binyamin Khan; Hajra Saddique; Bilal Saeed Khan; Saowaluck Tibpromma; Dao‐Chao Jin; Ting Chi Wen; Tian‐Ci Yi (New Zealand Journal of Botany, 2026)
The broad amplification potential of COI primers, typically designed for arthropods, unexpectedly revealed fungal DNA alongside arthropod data in our assessment of fungal communities across tropical (Hainan, China) and nontropical (Guizhou, China) rainforests using eDNA metabarcoding of 96 samples. This nontarget finding demonstrates the ability of COI‐based metabarcoding to capture fungal diversity in previously unexplored ambient samples. Our results showed very different biogeographical patterns. For example, in Hainan, mixed land use (MIX) resulted in a complete collapse of diversity (Shannon = 0.00), whereas in Guizhou, some diversity remained (Shannon = 0.28). In the tropics, diversity decreased by 90%; in the nontropics, by 64%. This increased sensitivity was associated with pronounced habitat specialization, as organic matter (OM) environments exhibited the highest diversity in Hainan (Shannon = 3.73). A GLM showed that OM had the biggest positive effect (estimate = 3.815, p p = 0.653). However, 33% of the Guizhou samples revealed a continuous lack of diversity over the years, indicating population extinction. The primary driver of community structure was habitat type, as confirmed by PERMANOVA ( R 2 = 0.301, p = 0.001). In the tropics, MIX resulted in an 87% loss of diversity, whereas in Guizhou the effects were nonsignificant ( p = 0.207). This indicates that tropical mushrooms are at risk of catastrophic collapse due to niche specialization, necessitating immediate protection of OM‐rich habitats. On the other hand, nontropical systems require restoration to address the instability caused by dispersal limitation.

Environmental policy stringency, renewable energy consumption, and load capacity factor in BRICS countries: a bootstrap rolling-window approach - Solomon Prince Nathaniel; Muhammad Saeed Meo; Olajide O. Oyadeyi; Chikaodili Josephine Solomon (Environment, Development and Sustainability, 2026)

Ligand modelling of Trachyspermum ammi phytocompounds for Aeromonas hydrophila cell wall synthesis enzyme in Labeo rohita - Muhammad Burhan Sabir; Aqeela Ashraf; Rashid Saif; Malaika Saeed; Muhammad Osama Zafar (Natural Product Research, 2026)

Investigation of photocatalytic efficiency and antimicrobial activity via Mn doped SnO2 using an eco-friendly green synthesis method - Laraib Bibi; Tahir Iqbal; Mariam Seemab; Sumera Afsheen; I.M. Ashraf; Faiza Saeed; Atif Mossad Ali; Muhammad Yousaf; M.A. Sayed (Journal of Environmental Chemical Engineering, 2026)

The transformative role of artificial intelligence in water resources engineering: A comprehensive review - Muhammad Rashid; Adan Saeed; Mohiq Khalid; Aniqa Murtaza; Muhammad Waqar Saleem (Environmental Modelling & Software, 2026)

Fuel-flexible flat-tubular solid oxide fuel cell stack for high performance and durable operation - Muhammad Haseeb Hassan; Saeed Ur Rehman; Syeda Youmnah Batool; Amjad Hussain; Rak-Hyun Song; Tak-Hyoung Lim; Jong-Eun Hong; Dong-Woo Joh; Seok-Joo Park; Hye-Sung Kim; Seung-Bok Lee (Chemical Engineering Journal, 2026)

Long-term subsoiling and no-tillage with moderate nitrogen regulate soil carbon sequestration, microbial cbbL expression, and maize yield under semi-arid plastic mulching - Umar Daraz; Junhong Xie; Lingling Li; Yongjie Zhou; Muhammad Farhan Saeed; Aftab Jamal (Plant and Soil, 2026)

Aflatoxin surveillance in Punjab’s dairy sector: feed and milk contamination - Naveed Akbar; Farhan Saeed; Muhammad Atif Randhawa; Sanaullah Iqbal; Asif Meraj; Abhayveer Singh; Bushra Niaz; T. Krithiga; Rajashree Panigrahi; Amara Rasheed; Zunaira Basharat; Muhammad Afzaal; et al. (Mycotoxin Research, 2026)

Biochar: Acinetobacter driven rhizoremediation of arsenic contaminated soil - Maria Hameed; Muhammad Umer; Maimona Saeed; Nageen Bostan; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

Antibiotic resistance dissemination in soil ecosystems: deep understanding for effective management and global health protection - Lu Li; Juexi Li; Saeed ur Rahman; Asad Rehman; Muhammad Khalid (BioMetals, 2026)

Synergistic efficacy of Azadirachta indica and biocontrol agents in mitigating Meloidogyne javanica infection in peach - Muhammad Saeed; Tariq Mukhtar; Raees Ahmed; Umair Mehmood; Muhammad Aamir Iqbal (Australasian Plant Pathology, 2026)

Antihyperlipidemic activity of Kalanchoe blossfeldiana leaf extract: phytochemical, in vitro, in vivo, and in silico insights - Abdul Rehman Riaz; Muhammad Islam; Hamid Saeed (In Silico Pharmacology, 2026)

Assessing the impact of nano-pollutants on the growth and development of stream breeding frogs - Isma Maqbool; Laraib Khadija; Muhammad Rais; Anila Rahim; Luqman; Muhammad Naveed Iqbal Raja; Zia-ur-Rehman Mashwani; Muhammad Shahbaz; Sumbul Gill; Muhammad Saeed (Biologia, 2026)

Magnoflorine and its structural diversity: mechanisms, and drug discovery opportunities a review - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Iqra Farzeen; Aamir Masood; Asma Ashraf (Molecular Diversity, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Enhancing resilience and sustainability: an inductive approach to innovations in cruise industry - Muhammad Hasan Ashraf; Naima Saeed; Kevin Cullinane; Martin Dresner (Transportation Research Part D: Transport and Environment, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

Natural resource wealth and corporate innovation: Governance, managerial discipline, and environmental management implications - Ahmad Ghazali; Muhammad Ashraf; Muhammad Saeed Meo; Khayrilla Kurbonov (Journal of Environmental Management, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Electrochemical detection of nitrite ions by solid-state synthesized Au2O3@NiO/ZnO nanocomposite for the environmental safety assessment - Mohammed Muzibur Rahman; Abdulkarim Albishri; Saeed D. Alahmari; Amjad E. Alsafrani; Nouf M. Alourfi; O. Madkhali; Roaa A. Tayeb; Muhammad Fazle Rabbee (Chemical Engineering Journal, 2026)

Thiamine and Indole-3-acetic Acid Mediated Detoxification of Arsenic in Maize to Improve Grain Proximate Components, Yield, and Nutrient Ingredients - Muhammad Atif; Shagufta Perveen; Farah Saeed; Abida Parveen; Sara Zafar; Naeem Iqbal (Water, Air, & Soil Pollution, 2026)

Wheat-Berseem intercropping system enhances soil fertility, carbon sequestration and crop productivity under nutrient-deficient conditions - Zafar Iqbal; Sundas Bilal; Sana ur Rehman; Imran Haider; Maryam Saeed; Maqshoof Ahmad; Muhammad Ali Raza; Mehraj A. Abbasov; Walid Soufan (Plant and Soil, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Exopolysaccharides Enhance Wheat Tolerance to Combined Salinity and Nickel Stress by Modulating Growth and Antioxidant Defense - Nabil Touzout; Meriem Babaali; Mahfoud Ainas; Aftab Jamal; Adil Mihoub; Iftikhar Ahmad; Subhan Danish; Muhammad Farhan Saeed; Árpád Székely (Journal of Plant Growth Regulation, 2026)

In-silico genome-wide identification of ADF gene family in Brassica napus under long-term high-temperature stress - Enerand Mackon; Shanshan Zhang; Zhuyu Pan; Muhammad Ikram; Latif Ullah Khan; Wajid Saeed; Muhammad Waseem; Yun Li; Pingwu Liu (Genetic Resources and Crop Evolution, 2026)

Balancing efficacy and resistance: oils vs. synthetic acaricides in the control of Panonychus citri - Muhammad Asif Qayyoum; Syed Husne Mobarak; Bilal Saeed Khan; Rehan Inayat; Asad Nawab; Tian-Ci Yi (Experimental and Applied Acarology, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

Temporal changes in soil dissimilarity are driven by synergistic effects of tree types and geographical distance in city parks - Saeed ur Rahman; Yucheng Bian; Xinxin Liu; Chang Zhao; Peiyuan Wang; Muhammad Khalid; Asad Rehman; Junfeng Cao; Noel Bruguera Amarán; Nan Hui (Landscape and Urban Planning, 2025)

Drosophila proteasome subunit Rpn8 controls IMD pathway activation via PGRP-SC2 degradation - Mingfei Wu; Umar Ali; Sen Ding; Chuchu Zhang; Yiheng Jin; Xinyan Cao; Muhammad Abdul Rehman Saeed; Yangyang Zhu; Muhammad Usama; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2025)

The role of catalytic subunit of AMPK in lipid accumulation in Mucor circinelloides WJ11 - Shuxian Pang; Futing Xue; Wu Yang; Hassan Mohamed; Jinghao Zhao; Muhammad Tariq Saeed; Chao Du; Qing Liu; Yuanda Song (Food Bioscience, 2025)

Retraction notice to “Development of reduced graphene oxide-supported novel hybrid nanomaterials (Bi2WO6@rGO and Cu-WO4@rGO) for green and efficient oxidative desulfurization of model fuel oil for environmental depollution” [Environ. Res., Part A, 212 (2022), 113160] - Aqsa Riaz; Muhammad Saeed; Mamoona Munir; Azeem Intisar; Sabah Haider; Shahzaib Tariq; Nazim Hussain; Rehana Kousar; Muhammad Bilal (Environmental Research, 2025)

Thiourea-modified silk cotton carbon as an efficient sulfur host: A green approach for advanced aluminum-sulfur battery - Muhammad Faheem; Arshad Hussain; Ananda Sholeh Rifky Hakim; Muhammad Ali; Abbas Saeed Hakeem; Md. Abdul Aziz (Biomass and Bioenergy, 2025)

Effect of okra polysaccharides extract powder on mixolab attributes, physicochemical characteristics and in-vitro starch digestibility of wheat bread - Mehak Fatima; Allah Rakha; Muhammad Saeed; Muhammad Shahid; Filip Van Bockstaele (Bioactive Carbohydrates and Dietary Fibre, 2025)

Advances in Microbial Bioremediation of Microplastics in Mangrove Sediments: a Comprehensive Review - Muhammad Sheeraz Javed; Muhammad Adil; Jiliang Zhang; Isma Gul; Muhammad Rauf; Saeed Ahmad; Bushra Moon; Siqi Lu; Heli Lu; Ali Haidar Gormani; Younas Iqbal; Hassan Mahmood (Water, Air, & Soil Pollution, 2025)

Modulating depression through the gut–brain axis: the role of gut microbiota in therapeutic interventions - Muhammad Muzammil Nazir; Warisha Ghaffar; Ghanva Mustafa; Saira Saeed; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Prevalence of New Delhi Metallo-β-lactamase (blaNDM) gene in a selected population of drug-resistant clinical isolates - Muhammad Shafiq; Aftab Ahmad; Kunza Latif; Muhammad Saeed; Iftikhar Ahmed; Muhammad Zeeshan Hyder (Molecular Biology Reports, 2025)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

CRISPR-Cas9 based editing of the susceptibility allele TaLr34 enhances leaf rust resistance in bread wheat without yield penalty - Muhammad Makky Javaid; Javed Ahmed; Moddassir Ahmed; Muhammad Jawad Akbar Awan; Muhammad Abu Bakar Waqas; Zahir Ali; Nasir A. Saeed (Functional & Integrative Genomics, 2025)

Integrating hematological profile and biomarker analysis for metals and metalloids ecotoxicological assessment on Wallago catfish and Indian carp health in Head Siphon, Mailsi, Pakistan - Kaynat Saeed; Sajid Abdullah; Muhammad Yaqoob; Minahal Fatima; Zunaira Majeed; Muhammad Ismail; Sara F. Ghanem; Moaheda E.H. Eissa; Hesham Hassanien; Zulhisyam Abdul Kari; El-Sayed Hemdan Eissa (BioMetals, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Paleoenvironmental and organic facies analysis of potential hydrocarbon source rocks in Surghar Range, Kohat Plateau - Arif Nazir; Fraz Khalid; Saeed Abbas; Muhammad Deen; Munawar Iqbal; Umer Younas; Muhammad Iftikhar Khan; Rab Nawaz (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Decarbonizing global value chains: The mediating role of economic upgrading in renewable energy transitions - Ghulam Muhammad Qamri; Li Sanchuan; Muhammad Saeed; Samariddin Makhmudov (Journal of Environmental Management, 2025)

Multi-objective fuzzy fractional-order BELBIC for semi-active seismic control in non-linear building structures - Muhammad Usman Saeed; Peizhen Li; Said Elias (Engineering Structures, 2025)

Sunlight responsive photo-oxidation of methylene blue dye using MgO/MnO2 nanoparticles - Hamza Laksaci; Nassima Djihane Zemani; Omar Khelifi; Muhammad Saeed; Badreddine Belhamdi; Abdelaziz Arroussi; Mohamed Trari (Colloids and Surfaces C: Environmental Aspects, 2025)

Assessing Heavy Metal Contamination and Health Risks in Urban Street Dust: Insights from Pakistan's Industrial Growth - Ahsan Riaz Khan; Adil Mihoub; Aftab Jamal; Muhammad Farhan Saeed; Somayeh Soltani-Gerdefaramarzi; Muhammad Irfan Ahamad (Water, Air, & Soil Pollution, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Current Insights into Heat Tolerance in Cereal Crops: From Molecular Mechanisms to Genome Editing Strategies - Muhammad Saeed (Journal of Plant Growth Regulation, 2025)

Efficacy and safety of cyclosporine in colitis: An updated meta-analysis of randomized control trials (1998 to 2024) - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Shaista Aslam; Adnan Haider; Muneeb Ullah; Jin-Wook Yoo; Rida Fatima Saeed; Muhammad Naeem (Inflammopharmacology, 2025)

Arbuscular mycorrhizal fungi and soil microbial communities under nitrogen deposition in nutrient-limited grasslands: a systematic review - Muhammad Numan Ali; Md Akramul Islam; Saddam Saqib; Muhammad Sufhan Tahir; Tahir Saadu; Ans Saeed; Aqarab Husnain Gondal (Symbiosis, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Synergistic effects of Ti3C2 MXene and ZIF-8 for efficient photocatalytic degradation of tetracycline in wastewater - Saeed Sajjadi; Michal Žitňan; Muhammad Umer Iqbal; Michal Machovský; Pedro Núñez; Dana Dvoranová; Dušan Galusek; Róbert Klement; Jose J. Velázquez (Journal of Environmental Chemical Engineering, 2025)

Unraveling the potential of zinc oxide nanoparticles on alleviating arsenic toxicity in wheat (Triticum aestivum L.) varieties: a comparative assessment of histology and phenomics - Eimaan Aamer; Muhammad Saeed; Faroha Liaqat; Muhammad Ramzan Khan; Muhammad Kashif Naeem; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Dose–response impact of arsenite on wheat (Triticum aestivum L.) genotypes: unravelling growth, accumulation, and antioxidant modulation for tolerance - Muhammad Saeed; Umar Masood Quraishi; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Isorhapontigenin: exploring a promising resveratrol analog for disease management through diverse signaling pathways—a review with computational insights - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Variations in the compositional profile of polycyclic aromatic moieties in coals from Bara, Patala and Salt Range formations: Insights into the mechanisms affecting the sedimentary record - Arif Nazir; Qaiser Hussain; Saeed Abbas; Fraz Khalid; Muhammad Deen; Abid Ali; Munawar Iqbal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The evolving role of biphasic solvents in CO2 capture: Recent developments, deployment challenges, and opportunities for AI-assisted screening - Ahmad Saeed; Muhammad Abdul Qyyum; DongYoung Lee; Rashid Al-Hajri (Chemical Engineering Journal, 2025)

Predicting ground-level PM 2.5 using high-resolution satellite imagery and machine learning algorithms with ground-based validation - Muhammad Hamza Tariq; Musawar Hussain; Muhammad Mahad Khaliq; Talha Saeed; Michael Howard Bergin; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Advancing the Accuracy of Anti-MRSA Peptide Prediction Through Integrating Multi-Source Protein Language Models - Watshara Shoombuatong; Pakpoom Mookdarsanit; Lawankorn Mookdarsanit; Nalini Schaduangrat; Saeed Ahmed; Muhammad Kabir; Pramote Chumnanpuen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

Improved early-stage crop classification using a novel fusion-based machine learning approach with Sentinel-2A and Landsat 8–9 data - Muhammad Daniyal Jamil; Muhammad Zahid Abbas; Muhammad Farhan Saeed; Aftab Jamal; Muhammad Mubeen; Ali Zakir; Iftikhar Ahmad; Rimsha Jameel; Katarzyna Pentoś; Yaser Hassan Dewir; Jakub Černý (Environmental Monitoring and Assessment, 2025)
Crop classification during the early stages is challenging because of the striking similarity in spectral and texture features among various crops. To improve classification accuracy, this study proposes a novel fusion-based deep learning approach. The approach integrates textural and spectral features from a fused dataset generated by merging Landsat 8–9 and Sentinel-2A data using the Gram-Schmidt fusion approach. The textural features were extracted using the multi-patch Gray Level Co-occurrence Matrix (GLCM) technique. The spectral features, namely the Enhanced Vegetation Index (EVI) and Normalized Difference Vegetation Index (NDVI), were obtained using the spectral index method. The five machine learning methods (deep neural network, 1D convolutional neural network, decision tree, support vector machine, and random forest) were trained using textural and spectral parameters to develop classifiers. The proposed approach achieves promising results using deep neural network (DNN), with an accuracy of 0.89, precision of 0.88, recall of 0.91, and F1-score of 0.90. These results demonstrate the effectiveness of the fusion-based deep learning approach in enhancing classification accuracy for early-stage crops.

Foliar Application of Ascorbic Acid and α-Tocopherol Enhances Salinity Tolerance in Hordeum vulgare L. by Regulating Antioxidant Enzymatic Activity and Improving Physiological and Biochemical Responses - Sadaf; Sami Ullah; Sikandar Shah; Aftab Jamal; Adil Mihoub; Muhammad Farhan Saeed; Iftikhar Ahmad; Emanuele Radicetti; Adil Zia; Andrea Mastinu; Jakub Černý (Journal of Crop Health, 2025)
Soil salinity severely impairs crop productivity by disrupting physiological and biochemical processes. This study investigated the efficacy of foliar-applied ascorbic acid (AsA) and α‑tocopherol (α-toc) in enhancing salinity tolerance in barley ( Hordeum vulgare L. cv. AJJ). A pot experiment using a randomized complete block design with three replicates was conducted under controlled conditions. Seedlings at the 4–5 leaf stage were exposed to 0, 40, or 80 mM NaCl salinity stress, followed by foliar treatments of AsA and α‑toc (150 mg L⁻ 1 ). Germination, agronomic, physiological, and biochemical parameters were analyzed. Salinity stress at 40 and 80 mM NaCl significantly reduced germination percentage (GP) by 18.6% and 18.4%, respectively, compared to the control (86.6%). Foliar application of AsA + α-toc under 40 and 80 mM stress restored GP to 82.3% and 81.7%, reflecting recoveries of 16.8% and 15.6% overstressed groups. Water content in leaves, shoots, and roots declined by 10–30% under salinity but improved by 15–25% with AsA + α-toc. Photosynthetic pigments were severely affected: chlorophyll a and total chlorophyll content (TCC) decreased by 45.7% (1.75 to 0.95 mg g⁻ 1 FW) and 10.9% (1.75 to 1.56 mg g⁻ 1 FW) at 40 and 80 mM NaCl, respectively. AsA + α-toc mitigated these losses, elevating TCC by 42.6% under 80 mM stress. Soluble protein content increased by 186% (0.50 to 1.43 mg g⁻ 1 ) under 80 mM stress but was stabilized by antioxidant treatments. Antioxidant enzymes, including superoxide dismutase (SOD) and peroxidase (POD), surged by 40–60% under salinity, while AsA + α-toc reduced hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) levels by 30–50%. The combined application of AsA and α‑toc proved most effective, enhancing stress tolerance through improved osmotic regulation, antioxidant defense, and chlorophyll preservation. These findings highlight the potential of AsA and α‑toc as sustainable agronomic tools for cultivating barley in saline soils, with AsA showing marginally greater efficacy. Further field studies are warranted to validate these results under different climatic conditions.

Improvement in lignin peroxidase oxidative stability via surface display by Bacillus subtilis - Na Shi; De Cheng; Yong Chen; Yong Feng; Muhammad Saeed; Zhongjian Guo; Zhaoyang Hu; Huayou Chen (Biotechnology Letters, 2025)

Impact of Climatic Variables on Fruit Bearing Behavior and Disease Incidence in Commercial Mango Cultivars in a Semi-arid Region - Hafiz Mohkum Hammad; Talal Tariq; Shafqat Saeed; Muhammad Tariq Malik; Hafiz Faiq Siddique; Rashid Jawad; Shah Fahad; Ifrah Kanwal; Aitazaz A. Farooque (Applied Fruit Science, 2025)

High-performance PVC/polyacrylate-graphene oxide membranes for Pb (II) and Hg (II) ion removal from polluted water: synthesis, characterization, and adsorption studies - Noreen Nasir; Junaid Raza; Abdul Hamid; Naseem Ahmad Khan; Mubushar Majeed; Muhammad Sohail Aslam; Anis Ali Shah; Muhammad Iftikhar; Bilal Arshad; Muhammad Sohail; Muhammad Saeed; Shifa Shaffique; et al. (Environmental Monitoring and Assessment, 2025)

Analyzing temporal changes in urban land use and climate dynamics through Google Earth Engine - Muhammad Zaib Arshad; Sajjad Hussain; Zafar Iqbal; Saeed Ahmad Qaisrani; Muhammad Mubeen; Muhammad Tahir; Shankar Karuppannan (Journal of Earth System Science, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

Identification of the blue-sky conditions in Punjab, Pakistan by exploiting satellite and ground-based observations, and policy implications - Hira Saif; Talha Saeed; Musawar Hussain; Afnan Ullah; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Resistance development, cross-resistance, and inheritance patterns in clothianidin and triazophos resistant strains of Oxycarenus hyalinipennis - Rabia Saeed; Naeem Abbas; Muhammad Akmal; Jam Nazir Ahmad (Crop Protection, 2025)

Unveiling three novel quantitative trait loci for leaf rust resistance in wheat (Anong-179 × PR-127 F2) - Farhan Ullah; Liaqat Shah; Muhammad Saeed; Chen Can; Si Hongqi; Ma Chuanxi (Physiological and Molecular Plant Pathology, 2025)

Impact of calcium modulation and starvation on fermentation-driven lipid accumulation in the oleaginous fungus Mucor circinelloides - Asmaa S. Ramadan; Hassan Mohamed; Huihui Xu; Adel Eltoukhy; Muhammad Tariq Saeed; Bushra Iqbal; Mohamed F. Awad; Xiuwen Wang; Wu Yang; Qing Liu; Yuanda Song (Food Bioscience, 2025)

WITHDRAWN:The effects of soybean protein on lipid profile, bone health in post-menopausal women, comparing healthy vs. hyperlipidemic individuals and safety evaluation in rats. - Muhammad Adnan Manzoor; Adeela Yasmeen; Farhan Saeed; Shumaila Kiran (Food and Humanity, 2025)

Micro and Nanoplastics in Ecosystems: Interrelated Sources, Risks, Pathways, Consequences, Mitigation, Challenges and Future Recommendations - Tauqeer Hussain; Muhammad Summer; Shaukat Ali; Rana Rashad Mahmood Khan; Muhammad Pervaiz; Zohaib Saeed (Water, Air, & Soil Pollution, 2025)

Evaluating the efficacy of nano-cyclosporine A in mice model of ulcerative colitis: a meta-analysis - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Nadia Shabnam; Adnan Haider; Shaista Aslam; Madiha Ghazanfar; Fakhar Ud-Din; Muhammad Irfan Siddique; Muhammad Naeem; Rida Fatima Saeed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Current Insights into the Molecular Mechanisms of Arsenic Tolerance in Wheat (Triticum aestivum L.) and Comparisons with Other Cereals - Muhammad Saeed; Gareth J. Norton; Riffat Naseem Malik (Journal of Plant Growth Regulation, 2025)

Kaempferol as a multi-targeted phytotherapeutic for arthritis: systematic review and meta-analysis of preclinical models - Muhammad Muzammil Nazir; Iqra Farzeen; Saira Saeed; Asma Ashraf (Inflammopharmacology, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Bioaccumulation of different heavy metals and toxicity assessment using different indices in grape plants and soil around power generators in Erbil province - Zhian Rashid Salih; Nashmeel Saeed Khudhur; Maqsuda Qadir Muhammad (Environmental Monitoring and Assessment, 2025)

Evaluating the effect of land use land cover changes on soil moisture index and vegetation indices using multi-spectral satellite data - Muhammad Zaib Arshad; Zafar Iqbal; Muhammad Saeed; Muhammad Saleem; Rizwan Mansha; M Abdullah-Al-Wadud; Aqil Tariq (Journal of Earth System Science, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Patho-physiological effects of environmental relevant concentrations of lufenuron in male Japanese quails - Silwat Saeed; Gulnaz Afzal; Hafiz Muhammad Ali; Riaz Hussain; Raheela Jabeen; Shumaila Kiran; Rehana Iqbal; Sana Alam; Amna Jalal; Zaib un Nisa; Dalia Fouad; Farid Shokry Ataya; et al. (Environmental Research, 2025)

Bending performance of a novel geopolymer non-dismantling sandwich insulation formwork: Experimental, theoretical, and numerical simulation - Shuang Li; Muhammad Sohail Saleh; Jianjun Zhao; Haoran Wang; Haopeng Liu; Muhammad Saeed Iqbal (Engineering Structures, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

Integrated Management of Nitrogen and Spent Mushroom Compost for Improved Wheat Yield and Soil Fertility - Uzair Ahmed; Aftab Jamal; Waleed Iqbal; Durrishahwar; Usama Qayyum; Muhammad Farhan Saeed; Amjad Ali; Domenico Ronga; Yaser Hassan Dewir; Jakub Černý (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Compost and Biogas Residues Reduces Soil and Pore Water Metal Concentration and Their Residual Toxicity to Wheat Seedlings - Iftikhar Ahmad; Ghulam Mustafa Shah; Hafiz Muhammad Shahbaz; Aftab Jamal; Muhammad Imtiaz Rashid; Muhammad Farhan Saeed; Amjad Farooq; Qasim Ali; Domenico Ronga (Journal of Soil Science and Plant Nutrition, 2025)

Characterization of date palm (Phoenix dactylifera L.) cultivars in Kech, Balochistan-Pakistan: antioxidant properties, phytochemical profiling and mineral composition - Muhammad Waseem; Summar Abbas Naqvi; Muhammad Jafar Jaskani; Faisal Saeed Awan (Genetic Resources and Crop Evolution, 2025)

Role of financial regulations and climate policy uncertainty in reducing CO2 emissions—an application of bootstrap subsample rolling-window Granger causality - Muhammad Saeed Meo; Tomiwa Sunday Adebayo (Clean Technologies and Environmental Policy, 2025)

Energy-related uncertainty, financial regulations, and environmental sustainability in the United States - Muhammad Saeed Meo; Alade Ayodeji Ademokoya; Attahir B. Abubakar (Clean Technologies and Environmental Policy, 2025)
The US has been classified as being “insufficient” by the Climate Action Tracker, indicating that the current actions and policies fall short of addressing critical environmental challenges. This suggests the need for enhancing the existing policy measures for improving environmental sustainability. To this end, this study investigates the time-varying impact of energy-related uncertainty and financial regulations on sectoral CO 2 emissions in the US. The bootstrap rolling-window Granger causality approach is employed to examine quarterly data spanning 1990Q1–2021Q4. The estimation results reveal that energy-related uncertainty increases CO 2 emissions in the transportation, residential, manufacturing, and construction sectors. On the other hand, financial regulations are found to reduce CO 2 emissions across the agricultural, transportation, residential, manufacturing, and construction sectors. The findings suggest the need for enhanced policy measures to improve energy stability and strengthen financial regulations focusing on climate-related disclosures and facilitating investments in low-carbon initiatives. Graphical abstract

In-vitro, in-vivo and computational experiments for the antidiabetic potential of bioactive compound from Notholirion thomsonianum - Abdulaziz Hassan Alhasaniah; Abdul Sadiq; Ahmed Abdullah Al Awadh; Yahya I. Asiri; Meriem Rezigue; Rehman Zafar; Sajjad Ahmad; Muhammad Saeed Jan; Mater H. Mahnashi (Natural Product Research, 2025)

RETRACTED ARTICLE: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2025)

A Potent Plant-Derived Chitinase: Structural Informatics and Insecticidal Activity against Helicoverpa armigera - Shah Rukh; Ahmed Akrem; Qamar Saeed; Sohaib Mehmood; Nosherwan Adil; Tazeen Rao; Muhammad Nasir; Uzma Ishaq; Aqal Zaman; Najeeb Ullah; Mohibullah Shah (Cell Biochemistry and Biophysics, 2025)

Synergistic defect engineering and z-scheme heterojunction in ultrasonication assisted CuFe LDH and carbon vacancies modified g-C3N4 composite for electrocatalytic water splitting and photocatalytic dye degradation - Muhammad Usman; Khurram Imran Khan; Samia; Sidra Khalid; Faiq Saeed; Abdul Wahab; Muhammad Sajjad Asghar; Ahmad Althobaiti; Alsharef Mohammad; Haitao Dai (Journal of Water Process Engineering, 2025)

Risk management strategies and climate change adoption policy: a global literature review using bibliometric analysis - Khush Dil Khan; Xuesong Guo; Tajdar Khan; Muhammad Saeed (Natural Hazards, 2025)

Impact of irrigation schedule and integrated nutrient management on wheat yield and nutrients uptake under semi-arid regions - Murad Ali; Abdul Bari; Muhammad Ibrahim; Iftikhar Ahmed; Uzair Ahmed; Rabia Zafar; Waqas Ahmad; Muhammad Saeed; Muhammad Khalid (Irrigation Science, 2025)

Exploring omics solutions to reduce micro/nanoplastic toxicity in plants: A comprehensive overview - Samia Muhammad Arif; Ilham Khan; Muhammad Saeed; Sunbal Khalil Chaudhari; Mansour Ghorbanpour; Murtaza Hasan; Ghazala Mustafa (Science of The Total Environment, 2025)

Shaping rhizocompartments and phyllosphere microbiomes and antibiotic resistance genes: The influence of different fertilizer regimes and biochar application - Kedi Li; Saeed ur Rahman; Asad Rehman; Haoxiang Li; Nan Hui; Muhammad Khalid (Journal of Hazardous Materials, 2025)

Greening road transport: Comparison of technologies in conventional, hybrid, and electric vehicles - Selin Karlilar Pata; Sinan Erdogan; Ugur Korkut Pata; Muhammad Saeed Meo (Journal of Environmental Management, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Self-nanoemulsifying drug delivery system for nebulization: fabrication and evaluation for systemic delivery of atorvastatin - Muhammad Danish Saeed; Kifayat Ullah Shah; Muhammad Fahad; Shefaat Ullah Shah; Syed Faisal Badshah; Hassan Shah; Irfan Anjum; Gamal A. Shazly; Mohammed Bourhia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Heavy Metal Concentrations in Water, Sediment, and Fish Species in Chashma Barrage, Indus River: A Comprehensive Health Risk Assessment - Khalid Hussain Rind; Sonia Aslam; Nazakat Hussain Memon; Asif Raza; Muhammad Qamar Saeed; Alia Mushtaq; Javed Ahmed Ujan; Syed Fahad Habib; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Environmentally friendly nitrogen doped paired mineral-carbon for catalytic degradation of diethyl phthalate and crop damage mitigation - Saeed Rehman; Hongjuan Sun; Muddasir Hanif; Tongjiang Peng; Xu Tang; Osama Tariq Satti; Muhammad Bilal (Chemical Engineering Journal, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Correction: Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

The influence of renewable energy, humanistic culture, and green knowledge on corporate social responsibility and corporate environmental performance - Muhammad Farhan Basheer; Saira Ghulam Hassan; Afshan Ali; Saeed Ahmad Sabir; Waeibrorheem Waemustafa (Clean Technologies and Environmental Policy, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Organic Food System: an overview and its challenges for healthy food systems - Wahyudi David; Raymond Auerbach; Susanne Gjedsted Bügel; Mahesh Chander; Muhammad Farhan Saeed; Lorena F. Hernandez; Maya Melati; Sonam Tashi; Siriwan Sinicom (Organic Agriculture, 2025)

Exploring the therapeutic potential of Ixora extract: a comprehensive review of mediated studies - Rabiyah Nadeem; Muhammad Imran; Zohaib Saeed; Muhammad Pervaiz; Umer Younas (Advances in Traditional Medicine, 2025)

A comprehensive review on guava: Nutritional profile, bioactive potential, and health-promoting properties of its pulp, peel, seeds, pomace and leaves - Farwa Iqbal Khan; Saeed Akhtar; Muhammad Qamar; Tariq Ismail; Wisha Saeed; Tuba Esatbeyoglu; Seid Mahdi Jafari (Trends in Food Science & Technology, 2025)

A global review on perfluoroalkyl acids (PFAAs) in the riverine systems: Environmental behaviours and risks implications - Muhammad Younas; Kifayatullah Khan; Maria Zeb; Muhammad Yaseen; Noor Samad Shah; Hassan Alshemmari; Yasar N. Kavil; Saeed Saad Alelyani; Mohamed Hussien; Sidra Zeb; Di Du (Science of The Total Environment, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

Spatial microenvironment enhanced photocatalytic reduction of uranyl ions under solar light irradiation - Xingnong Wu; Yishuo Zhang; Lingling Peng; Hao Jiang; Xiaoliang Liu; Shuang Zhang; Muhammad Saeed; Yonghui Liu; Yibao Liu; Tao Bo; Yuhui Liu; Xiaoyan Li (Journal of Hazardous Materials, 2025)

Addressing dye phytotoxicity and soil contamination: The dual action of chemically synthesized zinc nanoparticles in simultaneous adsorption and soil health improvement - Zainab Naseem; Muhammad Naveed; Saher Nawaz; Raafia Anam Saeed; Manzer H. Siddiqui; Adnan Mustafa; Avelino Núñez-Delgado (Journal of Environmental Management, 2025)

Retraction notice to “A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites” [Fuel 336 (2023) 126930] - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

Bio-templating approach and DFT study of ZrMo@KIT-6 catalyst for the conversion of deep fried oil into sustainable biodiesel production - Muhammad Noman; Muhammad Farooq; Anita Ramli; Ghazala Abid; Fouzia Perveen; Dur Muhammad; Rida Ihsan; Faizan Jamil; Ali Raza Ayub; Noor Saeed khattak; Ata Ur Rahman (Fuel, 2025)

Intermittent Fasting and Probiotics: Synergistic Modulation of Gut Health for Therapeutic Advantages - Amna Shehbaz; Muhammad Afzaal; Noor Akram; Farhan Saeed; Warda Khan; Faiyaz Ahmed; Aftab Ahmed; Aasma Asghar; Zargham Faisal (Probiotics and Antimicrobial Proteins, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

Comparative Nutritional Profiling of Economically Important Shrimp Species in Pakistan - Muhammad Bhatti; Shahid Sherzada; Sohail Ahmad; Muhammad Qazi; Amina Ayub; Saeed Khan; Muhammad Khan; Iqra Rani; Nimra Hussain; Joanna Nowosad; Dariusz Kucharczyk (Journal of Marine Science and Engineering, 2025)
Shrimp are widely recognized as a nutritious and flavorful food choice due to their tender and delicious meat. This study evaluated the nutritional composition of three economically important shrimp species: Penaeus merguiensis, Penaeus monodon, and Penaeus indicus, collected from the coastal areas of Pakistan. All shrimp species were found to be high in protein and low in fat content. The ratio of essential amino acids (EAAs), non-essential amino acids (NEAAs), and total amino acids (TAAs) varied significantly (p ≤ 0.05) among species, with P. indicus showing slightly higher values. Regarding fatty acid analysis, total saturated fatty acid content was found to be 35.04% in P. merguiensis, 52.43% in P. monodon, and 44.77% in P. indicus. Similarly, the polyunsaturated fatty acid content was found to be 26.24%, 26.77%, and 24.74%, in P. merguiensis, P. monodon, and P. indicus, respectively. Based on nutrient yield, P. monodon stands out as the most nutrient-dense species, followed by P. indicus and P. merguiensis. Overall, the present study suggests that all shrimp species can be used as a healthy choice of food and a good source of animal protein for human consumption. These findings provide valuable insights into the role of shrimp in promoting a healthy and balanced diet.

Cross-climatic comparison of microbial stress-responsive genes in urban parks: A comparative analysis - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Chang Zhao; Haoxin Tan; Samiah Arif; Bangxiao Zheng; Yucheng Bian; Ari Jumpponen; D. Johan Kotze; et al. (Urban Forestry & Urban Greening, 2025)

A comprehensive review of approaches, systems, and materials used in adsorption-based atmospheric water harvesting - Muhammad Ehtisham; Muhammad Saeed-Ul-Hassan; Albert Poater (Science of The Total Environment, 2025)

Sublethal Concentrations of Cadmium and Lead: Effects on Hemato-Biochemical Parameters and Tissue Accumulation in Wallagu attu - Rim EL Amouri; Javed Ahmed Ujan; Asif Raza; Alia Mushtaq; Muhammad Qamar Saeed; Samrah Masud; Syed Sikandar Habib; Marija Milošević; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Dyna-PINN: Physics-informed deep dyna-q reinforcement learning for intelligent control of building heating system in low-diversity training data regimes - Muhammad Hafeez Saeed; Hussain Kazmi; Geert Deconinck (Energy and Buildings, 2024)

Prevalence and associated risk factors of Brucella abortus and Brucella melitensis in humans and cattle populations: A comprehensive study - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Molecular prevalence, phylogenetic analysis, and PCR-based detection of Brucella melitensis in humans and cattle in Southern Khyber Pakhtunkhwa, Pakistan - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

Diagnostic and therapeutic value of EVs in lungs diseases and inflammation - Ali Afzal; Muhammad Babar Khawar; Ume Habiba; Hanan Afzal; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Rimsha Abaidullah; Zoya Asif; Tahaa Saeed (Molecular Biology Reports, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

Conjoint effect of indole-3-acetic acid and vitamin B1 on nutrient acquisition and seed oil physicochemical properties of Zea mays L. under arsenic intervention - Muhammad Atif; Shagufta Perveen; Abida Parveen; Farah Saeed (Journal of Plant Growth Regulation, 2024)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Movement of amphibians in a habitat mosaic of agriculture landscape - Waseem Ahmed; Muhammad Rais; Ayesha Akram; Muhammad Saeed; Luqman; Sumbul Gill; Aamina Abid; Abdul Hadi (European Journal of Wildlife Research, 2024)

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Understanding how climate preferences, environmental policy stringency, and energy policy uncertainty shape renewable energy investments in Germany - Muhammad Saeed Meo; Naila Erum; Hicham Ayad (Clean Technologies and Environmental Policy, 2024)

Analyzing the effects of solar energy innovations, digitalization, and economic globalization on environmental quality in the United States - Tomiwa Sunday Adebayo; Muhammad Saeed Meo; Babatunde Sunday Eweade; Oktay Özkan (Clean Technologies and Environmental Policy, 2024)
The escalating apprehension regarding climate change mitigation has intensified the quest for energy alternatives that are low in carbon emissions, economically viable, and consistently available. Within this context, renewable energy sources emerge as fitting candidates, being recognized for their eco-friendliness and cleanliness. Nonetheless, despite the allure of transitioning towards cleaner energy, there exists a notable dearth of literature addressing the pivotal role of solar energy innovations and economic globalization in advancing the agenda of climate change mitigation (SDG-13), thus complicating the prediction of factors influencing ecological quality. Consequently, this study undertakes the inaugural investigation into the impact of solar energy innovation on ecological footprint, while also considering the influences of digitalization, economic globalization, renewable energy, and natural resources in the USA. To this end, Quantile-on-Quantile Kernel-Based Regularized Least Squares (QQKRLS) and wavelet quantile regressions (WQR) methodologies are employed, utilizing data spanning from 2000 to 2020. The analysis reveals that solar energy innovation, along with renewable energy, digitalization, and economic globalization, exerts a negative impact on ecological footprint, whereas natural resources exhibit a positive influence. Drawing from these insights, it becomes apparent that a concerted effort from stakeholders and policymakers is imperative in realizing the objectives of SDG-13 and SDG-7, necessitating a paradigm shifts in the USA’s energy portfolio away from fossil fuels towards renewables. Graphical abstract

Impact of seismotectonic source zoning and seismic parameter: Sensitivity study on probabilistic seismic hazard assessment - Muhammad Salman Ali; Kashif Saeed; Luo Dong; Ma Jianxun (Soil Dynamics and Earthquake Engineering, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

Dimerized Non-Fullerene Acceptor-based organic photovoltaics for Round-the-Clock functioning - Hyeon Su Kim; Xuyao Song; Muhammad Ahsan Saeed; Gyeong Min Lee; Hyungju Ahn; Yun-Hi Kim; Jae Won Shim (Chemical Engineering Journal, 2024)

Risk and retraction: asymmetric nexus between monetary policy uncertainty and eco-friendly investment - Lansheng Cao; Ding Jin; Sajid Ali; Muhammad Saeed Meo; Raima Nazar (Stochastic Environmental Research and Risk Assessment, 2024)

Biochemical analysis and fertilization success of Cirrhinus mrigala ova during induced spawning - Shahid Sherzada; Tanveer Ahmad; Saeed Akram Khan; Muhammad Inayat; Sohail Ahmad; Abdur Rahman (Animal Reproduction Science, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Use of Metallic Nanoparticles Against Eimeria—the Coccidiosis-Causing Agents: A Comprehensive Review - Sahar Mustafa; Rao Zahid Abbas; Zohaib Saeed; Narjes Baazaoui; Arslan Muhammad Ali Khan (Biological Trace Element Research, 2024)

Bovine colostrum: Therapeutic potential and clinical evidence - Talha Shireen Khan; Noor Akram; Zargham Faisal; Farhan Saeed; Amara Rasheed; Faiyaz Ahmed; Muhammad Afzaal (International Dairy Journal, 2024)

Nutritional benefits of bioactive compounds from watermelon: A comprehensive review - Parkash Meghwar; Syed Muhammad Ghufran Saeed; Asad Ullah; Emmanuel Nikolakakis; Eirini Panagopoulou; Alexandros Tsoupras; Slim Smaoui; Amin Mousavi Khaneghah (Food Bioscience, 2024)

Effect of electrolyzed watermelon rind flour on unleavened flatbread quality, techno-functional properties, minerals, bioactivities, and consumer preferences - Parkash Meghwar; Syed Muhammad Ghufran Saeed; Alexandros Tsoupras; Rana Muhammad Aadil; Isaac Duah Boateng (Food Bioscience, 2024)

Nanoparticle-mediated modulation of plant performance and microbiome dynamics: Insights into interplay mechanisms - Kedi Li; Haoxiang Li; Saeed ur Rahman; Asad Rehman; Muhammad Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

In vitro and in vivo modulatory effects of fluoxetine on gene expression and antioxidant enzymes in CFA-induced chronic inflammatory model: drug repurposing for arthritis - Hafiz Muhammad Irfan; Awais Anjum; Mulazim Hussain Asim; Saeed Ur Rasheed; Alamgeer; Farzana Siddique (Inflammopharmacology, 2024)

Retraction Note: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2024)

Microplastic pollution in aquatic ecosystem: A review of existing policies and regulations - Muhammad Tariq Khan; Sajid Rashid; Unzile Yaman; Saeed Ahsan Khalid; Asif Kamal; Mushtaq Ahmad; Nasrin Akther; Md Abul Kashem; Md Faysal Hossain; Wajid Rashid (Chemosphere, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

Metabolites-induced co-evolutionary warfare between plants, viruses, and their associated vectors: So close yet so far away - Naveed Ahmad; Hamad Hussain; Muhammad Naeem; Saeed ur Rahman; Khalid Ali Khan; Babar Iqbal; Abdul Wakeel Umar (Plant Science, 2024)

From port to planet: Assessing NO2 pollution and climate change effects with Sentinel-5p satellite imagery in maritime zones - Mohd Azhafiz Abdullah; L.F. Chuah; Samsuri Bin Abdullah; Awais Bokhari; Asad Syed; Abdallah M. Elgorban; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman; Saira Asif (Environmental Research, 2024)

Mitigating potential of polystyrene microplastics on bioavailability, uptake, and toxicity of copper in maize (Zea mays L.) - Muhammad Saad Bashir; Umair Saeed; Jawad Aslam Khan; Muhammad Saeed; Ghazala Mustafa; Riffat Naseem Malik (Environmental Pollution, 2024)

Bidentate mode coordinated Ti3CNTx MXene-controlled interfacial engineering enables high-performance indoor organic photovoltaic devices - Muhammad Ahsan Saeed; Zubair Khalid; Min Jong Lee; Hyungju Ahn; Jae-Min Oh; Jae Won Shim (Chemical Engineering Journal, 2024)

Pharmacogenetic study of CES1 gene and enalapril efficacy - Misbah Hussain; Sehrish Basheer; Adila Khalil; Qurat Ul Ain Haider; Hafsa Saeed; Muhammad Faizan (Journal of Applied Genetics, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Effects of drought on morpho-physiological attributes and secondary metabolites of wheat genotypes: Growth traits, seed yield and stress tolerance indices - Jazia Naseem; Qasim Ali; Farah Saeed; Rashida Perveen; Muhammad Rizwan (South African Journal of Botany, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Robust deep learning based shrimp counting in an industrial farm setting - Christina Bukas; Frauke Albrecht; Muhammad Saeed Ur- Rehman; Daniel Popek; Mikołaj Patalan; Jarosław Pawłowski; Bert Wecker; Kilian Landsch; Tomasz Golan; Tomasz Kowalczyk; Marie Piraud; Stephan S.W. Ende (Journal of Cleaner Production, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Assessment of heavy metal levels in polyculture fish farms and their aquatic ecosystems: an integrative study addressing environmental and human health risks associated with dam water usage - Syed Sikandar Habib; Saira Naz; Muhammad Qamar Saeed; Javed Ahmed Ujan; Samrah Masud; Alia Mushtaq; Mujeeb Ullah; Khalid Khan; Muhammad Zahid; Salim S. Al-Rejaie; Mohamed Mohany (Environmental Geochemistry and Health, 2024)

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

A multiplex PCR assay to detect mislabelling in fish products - Komal; Shahid Sherzada; Muhammad Imran; Saeed Akram Khan; Abdul Wajid (Food Additives & Contaminants Part B-Surveillance, 2024)

Retraction Note: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2024)

Holistic insight mechanism of ozone-based oxidation process for wastewater treatment - Ghazala Akber Jamali; Satesh Kumar Devrajani; Sheeraz Ahmed Memon; Sundus Saeed Qureshi; Gnanasambandam Anbuchezhiyan; Nabisab Mujawar Mubarak; S.Z.M. Shamshuddin; Muhammad Tahir Hussain Siddiqui (Chemosphere, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Evaluating climate change impacts on reef environments via multibeam echosounder and Acoustic Doppler Current profiler technology - Mohd Azhafiz Abdullah; L.F. Chuah; Razak Zakariya; Asad Syed; Rozaimi Che Hasan; Shahrul Miza Mahmud; Abdallah M. Elgorban; A. Bokhari; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman (Environmental Research, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Sustainability in shaky times: analysing the resilience of green bonds amid economic policy uncertainty - Xichen Liu; Sajid Ali; Raima Nazar; Muhammad Saeed Meo (Stochastic Environmental Research and Risk Assessment, 2024)

Monitoring insecticide resistance in Bemisia tabaci mitotypes in the South Punjab region of Pakistan - Rao Muhammad Shamraiz; Shafqat Saeed; Mirza Abdul Qayyum; Zulqurnain Khan (International Journal of Tropical Insect Science, 2024)

Recent Progress of Fluorescent Carbon Dots and Graphene Quantum Dots for Biosensors: Synthesis of Solution Methods and their Medical Applications - Rafaqat Khan; Amina Qureshi; Muhammad Azhar; Zia Ul Hassan; Sagheer Gul; Saeed Ahmad (Journal of Fluorescence, 2024)

Quantifying the role of logic tree parameters in soil probabilistic seismic hazard assessment: Insights from sensitivity analysis - Muhammad Salman Ali; Kashif Saeed; Luo Dong; Ma Jianxun (Soil Dynamics and Earthquake Engineering, 2024)

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Metabolomics profiling reveals the detoxification and tolerance behavior of two bread wheat (Triticum aestivum L.) varieties under arsenate stress - Muhammad Saeed; Umar Masood Quraishi; Ghazala Mustafa; Abida Farooqi; Maria Greger; Riffat Naseem Malik (Food Chemistry, 2024)

Maize bran arabinoxylans mediated green synthesis of silver nanoparticles and their incorporation in gelatin-based packaging film - Muhammad Ahtisham Raza; Awais Ahmad; Farhan Saeed; Muzzamal Hussain; Muhammad Afzaal; Amara Rasheed (Food Packaging and Shelf Life, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

Two-dimensional MXenes: A route from synthesis to applications in self-powered IoT devices - Muhammad Ahsan Saeed; Muhammad Zain Qamar; Zubair Khalid; Elham Chamanehpour; Yogendra Kumar Mishra (Chemical Engineering Journal, 2024)

Bacillus subtilis: current and future modification strategies as a protein secreting factory - Yanzhen Chen; Miaomiao Li; Mingchen Yan; Yong Chen; Muhammad Saeed; Zhong Ni; Zhen Fang; Huayou Chen (World Journal of Microbiology and Biotechnology, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

Comparative genomic studies on the TGF-β superfamily in blue whale - Zunaira Faiz; Shakeela Parveen; Saba Saeed; Muhammad Tayyab; Mehwish Sultana; Muhammad Hussain; Zainab Shafqat (Mammalian Genome, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Combined Effect of Biochar and Plant Growth-Promoting Rhizbacteria on Physiological Responses of Canola (Brassica napus L.) Subjected to Drought Stress - Gul-Lalay; Sami Ullah; Sikandar Shah; Aftab Jamal; Muhammad Farhan Saeed; Adil Mihoub; Adil Zia; Iftikhar Ahmed; Mahmoud F. Seleiman; Roberto Mancinelli; Emanuele Radicetti (Journal of Plant Growth Regulation, 2024)
Biochar (BC) and plant growth-promoting microbes (PGPR) could represent a suitable agronomical strategy to mitigate the impacts of drought in arid agro-environmental conditions. However, there is currently little understanding of the synergistic benefit of combining BC and PGPR to increase drought tolerance in oilseeds. In this study, the physiological response of two water-stressed canola ( Brassica napus L.) plants subjected to the application of BC obtained from waste wood of Morus alba applied solely or in combination with PGPR strains ( Pseudomonas sp.) was evaluated. The experiment consists of two genotypes and nine treatments [(C-Control, T1-15 days drought (15DD), T2-30 days drought (30DD), T3-15 days of drought + PG (15DD + PG), T4-30 days of drought + PG (30DD + PG), T5-15 days drought + biochar (15DD + BC), T6-30 days drought + biochar (30DD + BC), T7-15 days drought + biochar + PG (15DD + BC + PG), T8-30 days drought + biochar + PG (30DD + BC + PG)]. Drought stress decreased emergence energy (EE), leaf area index (LAI), leaf area ratio (LAR), root shoot ratio (RSR), moisture content of leaves (MCL), percent moisture content (%MC), moisture content of shoot (MCS) and moisture content of root (MCR), and relative water content (RWC) in both varieties of Brassica napus L., which in contrast, it is increased by the collective application of both biochar and PGPR. In both varieties, N, P, K, Mg, and Ca concentrations were highest in all the biochar and PGPRs separate and combined treatments, while lowest in 15 and 30 days drought treatments. Osmolyte contents like Glycine betaine (GB) and sugar remarkably increased in the stress condition and then reduced due to the synergistic application of biochar and PGPR. Drought stress has a repressive effect on the antioxidant enzymatic system like Peroxidase (POD), Superoxide dismutase (SOD), and glutathione reductase (GR) as well as total flavonoids, phenolics, and protein content. The antioxidant enzymes and phenolic compounds were dramatically increased by the combined action of biochar and PGPRs. A significant increase in EE, LAR, RSR, and RWC under 15 and 30 days drought conditions, evidently highlighting the synergistic effect of BC and PGPR. The results conclude a substantial and positive effect of the combined use of BC and PGPR strains on canola's response to induced drought stress, by regulating the physiological, biochemical, and agronomic traits of the plants. Graphical Abstract

A Computational Predictor for Accurate Identification of Tumor Homing Peptides by Integrating Sequential and Deep BiLSTM Features - Roha Arif; Sameera Kanwal; Saeed Ahmed; Muhammad Kabir (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Analyzing the impact of pesticides on the indus river: contamination levels in water, sediment, fish, and associated human health risks - Syed Sikandar Habib; Francesco Fazio; Samrah Masud; Javed Ahmed Ujan; Muhammad Qamar Saeed; Mujeeb Ullah; Khalid Khan; Khayyam Khayyam; Mohamed Mohany; Marija Milošević; Salim S. Al-Rejaie; Cristina Cravana (Environmental Geochemistry and Health, 2024)

Deep soil seismic hazard assessment: analyzing the impact of local site effects by stochastic site response analysis—a comparative approach - Muhammad Salman Ali; Kashif Saeed; Ma Jianxun; Luo Dong; Liaqat Ali (Bulletin of Engineering Geology and the Environment, 2024)

Novel polynomial Abet data augmentation algorithm with GRU paradigm for nuclear power prediction - Saifullah Khan; Saeed Ehsan Awan; Yasir Muhammad; Ihtesham Jadoon; Muhammad Asif Zahoor Raja (Annals of Nuclear Energy, 2024)

Shear damage repair of masonry walls using different materials - Ahmed Mohamed Raouf; Jalal Ahmed Saeed; Muhammad Raouf Abdul-Kadir; Sarwat Hassan Ahmed (European Journal of Environmental and Civil Engineering, 2024)

Sustainable performance and disaster management in the oil and gas industry: An intellectual capital perspective - Sajid Nazir; Mahmood Ali; Munazza Saeed; Muhammad Shahzad Mubarik; Qasim Jalil (Resources Policy, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Financial regulations and sustainability: The role of energy price and climate policy uncertainty - Muhammad Shahbaz; Muhammad Saeed Meo; Hafiz Waqas Kamran; Muhammad Saif ul Islam (Journal of Environmental Management, 2024)

Ultrahigh-performance indoor perovskite quantum dot photovoltaics via ligand-passivation engineering - Seon Joong Kim; Muhammad Ahsan Saeed; Tae Hyuk Kim; Gayoung Ham; Hochan Song; Hyungju Ahn; Hyosung Choi; Jea Woong Jo; Yunsang Kim; Hyojung Cha; Jae Won Shim (Chemical Engineering Journal, 2024)

Microbial goldmine: Investigating probiotic floral diversity in human breast milk - Ayesha Saeed; Azra Yasmin; Mehreen Baig; Maryam Pervaiz; Muhammad Arslan Ahmed; Muhammad Tabish; Humaira Hashmat (Bioactive Carbohydrates and Dietary Fibre, 2024)

Sunlight-Driven Photocatalytic Degradation of Methylene Violet (MV) by Employing Samarium-Doped Tungsten Disulfide - Saba Zahra; Meznah M. Alanazi; Shaimaa A. M. Abdelmohsen; Saeed D. Alahmari; Fatimah A. M. Al-Zahrani; Abdullah G. Al-Sehemi; A. M. A. Henaish; Zubair Ahmad; Hafiz Muhammad Tahir Farid (Water, Air, & Soil Pollution, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Middle Miocene “Giraffa” from the Chinji Formation of Siwaliks, Pakistan - Muhammad Asim; Kiran Aftab; Muhammad Akbar Khan; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mubashar Hussain; Sania Saeed (Palaeoworld, 2024)

Effects of pulsed Nd:YAG laser kernel irradiation on maize (Zea mays L.): Insights into germination, gas exchange, photosynthetic pigments, and morphological modifications - Rashida Perveen; Yasir Jamil; Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Qasim Ali; Farah Saeed; Muhammad Azeem; Muhammad Rizwan; Sami Asir Al-Robai (Journal of Photochemistry and Photobiology B: Biology, 2024)

Exploring the impact of urbanization and vegetation type on fungal communities: Insights into divergent, mycorrhizal, and saprophytic associations driven by climate patterns - Muhammad Khalid; Saeed ur Rahman; Xinxin Liu; Asad Rehman; Ari Jumpponen; D. Johan Kotze; Heikki Setälä; Nan Hui (CATENA, 2024)

Plant-mediated green synthesis of silver nanoparticles: Synthesis, characterization, biological applications, and toxicological considerations: A review - Zarfishan Zulfiqar; Rana Rashad Mahmood Khan; Muhammad Summer; Zohaib Saeed; Muhammad Pervaiz; Shahzad Rasheed; Behram Shehzad; Fatima Kabir; Saira Ishaq (Biocatalysis and Agricultural Biotechnology, 2024)

Isolation, invitro, invivo anti-inflammatory, analgesic and antioxidant potential of Habenaria plantegania Lindl - Osama M. Alshehri; Madeeha Shabnam; Saeed Ahmed Asiri; Mater H. Mahnashi; Abdul Sadiq; Muhammad Saeed Jan (Inflammopharmacology, 2024)

Retraction Note: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2024)

Retraction Note: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Optimization of multi-stage micellar-enhanced flocculation process for removal of Levofloxacin hemihydrate in wastewater - Fiza Bukhtawar; Muhammad Usman; Atta Ul Haq; Muhammad Saeed; Atif Saleem (Journal of Water Process Engineering, 2024)

Identification and Annotation of the 21 Novel Sugar Cane (Saccharum officinarum) MicroRNA Clusters and Their Significant Biological, Molecular and Cellular Targets - Abdul Baqi; Samiullah; Muhammad Zafar Saleem; Muhammad Ayub; Shazia Saeed (Tropical Plant Biology, 2024)

Protective role of manganese, proline and rice straw extract in wheat against drought driven oxidative stress - Abida Parveen; Shagufta Perveen; Sana Tariq; Muhammad Atif; Farah Saeed; Sara Zafar (Acta Physiologiae Plantarum, 2024)

Mechanism and synergistic effect of sulfadiazine (SDZ) and cadmium toxicity in spinach (Spinacia oleracea L.) and its alleviation through zinc fortification - Muhammad Nafees; Adiba Khan Sehrish; Sarah Owdah Alomrani; Linlin Qiu; Aasim Saeed; Shoaib Ahmad; Shafaqat Ali; Hongyan Guo (Journal of Hazardous Materials, 2024)

Hydrothermal synthesis of ZnO@MoTe2 nanocomposite as excellent electrocatalyst for hydrogen evolution reaction (HER) - Saeed D. Alahmari; Salma Aman; Soumaya Gouadria; Sajjad Ahmad Khan; Abdullah G. Al-Sehemi; A.M.A. Henaish; Naseeb Ahmad; Zubair Ahmad; Taha Abdel Mohaymen Taha; Hafiz Muhammad Tahir Farid (Fuel, 2024)

Sustainable humidity control in the built environment: Recent research and technological advancements in thermal driven dehumidification systems - Muhammad Usman Saeed Akhtar; Sulaiman O. Fadlallah; Muhammad Imran Khan; Faisal Asfand; Sami G. Al-Ghamdi; Rakesh Mishra (Energy and Buildings, 2024)

Tailoring hole-selective contacts via self-assembled monolayers for advancing indoor organic photovoltaic and capacitor devices - Min Jong Lee; Ji-Sang Park; Tae Hyuk Kim; Muhammad Ahsan Saeed; Gyeong Min Lee; Jae Won Shim (Chemical Engineering Journal, 2024)

2-Hydroxybenzohydrazide as a novel potential candidate against nociception, inflammation, and pyrexia: in vitro, in vivo, and computational approaches - Gowhar Ali; Nazar Ul Islam; Muhammad Qaim; Rahim Ullah; Muhammad Saeed Jan; Khadija Shabbiri; Muhammad Shafique; Muhammad Ayaz (Inflammopharmacology, 2024)

Revisiting the environmental Kuznets curve: assessing the impact of climate policy uncertainty in the Belt and Road Initiative - Yi Huang; Saif Ur Rahman; Muhammad Saeed Meo; Muhammad Sibt E. Ali; Sarwar Khan (Environmental Science and Pollution Research, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Arsenic accumulation pattern in water-soil-rice systems: A study of tolerance mechanisms and associated health risks - Muhammad Saeed; Muhammad Anas; Umar Masood Quraishi; Riffat Naseem Malik (Science of The Total Environment, 2024)

Biosynthesized zinc oxide nanoparticles modulate the phytoremediation potential of Pennisetum giganteum and its rhizocompartments associated microbial community structure - Haoxiang Li; Asad Rehman; Saeed ur Rahman; Kedi Li; Tianrui Yang; Percy Akuetteh; Muhammad Khalid (Journal of Cleaner Production, 2024)

Decarbonising ASEAN coastal shipping: Addressing climate change and coastal ecosystem issues through sustainable carbon neutrality strategies - Olakunle Oloruntobi; Lai Fatt Chuah; Kasypi Mokhtar; Adel Gohari; Ahmed Rady; Rasha E. Abo-Eleneen; Muhammad Saeed Akhtar; Muhammad Mubashir (Environmental Research, 2024)

The flexible linker and CotG were more effective for the spore surface display of keratinase KERQ7 - Zhen Wang; Mingchen Yan; Muhammad Saeed; Keyi Li; Yanzhen Chen; Charles Obinwanne Okoye; Zhen Fang; Zhong Ni; Huayou Chen (World Journal of Microbiology and Biotechnology, 2024)

Phenomic profiling to reveal tolerance mechanisms and regulation of ascorbate–glutathione cycle in wheat varieties (Triticum aestivum L.) under arsenic stress - Muhammad Saeed; Umar Masood Quraishi; Tommy Landberg; Maria Greger; Riffat Naseem Malik (Environmental Geochemistry and Health, 2024)

Genome-wide identification and characterization of wall-associated kinases, molecular docking and polysaccharide elicitation of monoterpenoid indole alkaloids in micro-propagated Catharanthus roseus - Jawad Ahmed; Yasar Sajjad; Aasia Latif; Mohammad Saeed Lodhi; Muhammad Huzafa; Chen Situ; Raza Ahmad; Muhammad Maroof Shah; Amjad Hassan (Journal of Plant Research, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Plant-based foods and hepatocellular carcinoma: A review on mechanistic understanding - Raakia Anam Saeed; Maria Maqsood; Raafia Anam Saeed; Hafiz Shehzad Muzammil; Muhammad Issa Khan; Laiba Asghar; Sahar Un Nisa; Roshina Rabail; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2023)

RETRACTED: Responses of microbial communities in rhizocompartments of king grass to phytoremediation of cadmium-contaminated soil - Muhammad Khalid; Xinxin Liu; Saeed ur Rahman; Asad Rehman; Chang Zhao; Xiaoxiao Li; Bian Yucheng; Nan Hui (Science of The Total Environment, 2023)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

Assessing coastal bathymetry and climate change impacts on coastal ecosystems using Landsat 8 and Sentinel-2 satellite imagery - Kasypi Mokhtar; Lai Fatt Chuah; Mohd Azhafiz Abdullah; Olakunle Oloruntobi; Siti Marsila Mhd Ruslan; Gadah Albasher; Atif Ali; Muhammad Saeed Akhtar (Environmental Research, 2023)

Developing energy flexibility in clusters of buildings: A critical analysis of barriers from planning to operation - Jérôme Le Dréau; Rui Amaral Lopes; Sarah O'Connell; Donal Finn; Maomao Hu; Humberto Queiroz; Dani Alexander; Andrew Satchwell; Doris Österreicher; Ben Polly; Alessia Arteconi; Flavia de Andrade Pereira; et al. (Energy and Buildings, 2023)

Silver hybridized polymer nanocomposite for efficient encapsulation of toxic dye from aqueous solution - Muhammad Amjad; Ayesha Mohyuddin; Wajad Ulfat; Saeed Ahmed; Abrar Ul Hassan (Nanotechnology for Environmental Engineering, 2023)

Intervening Role of Tyrosine in Cadmium Detoxification, Balancing of Mineral Ions Homeostasis, Antioxidants, and Secondary Metabolites in Maize - Muhammad Atif; Shagufta Perveen; Abida Parveen; Sara Zafar; Fatima Batool; Farah Saeed (Journal of Soil Science and Plant Nutrition, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Differential Response of Two Contrasting Melon (Cucumis melo L.) Genotypes to Drought Stress - Asad Rehman; Jinyang Weng; Pengli Li; Jing Yu; Saeed ur Rahman; Muhammad Khalid; Iftikhar Hussain Shah; Shazma Gulzar; Liying Chang; Qingliang Niu (Journal of Plant Biology, 2023)

Dinuclear gold(I) complexes based on carbene and diphosphane ligands: bis[2-(dicyclohexylphosphano)ethyl]amine complex inhibits the proteasome activity, decreases stem cell markers and spheroid viability in lung cancer cells - Naike Casagrande; Cinzia Borghese; Giuseppe Corona; Donatella Aldinucci; Muhammad Altaf; Adam A. A. Sulaiman; Anvarhusein A. Isab; Saeed Ahmad; Abdul Malik P. Peedikakkal (JBIC Journal of Biological Inorganic Chemistry, 2023)

National strategy for climate change adaptability: a case study of extreme climate-vulnerable countries - Noman Arshed; Muhammad Ibrahim Saeed; Sultan Salem; Uzma Hanif; Manzir Abbas (Environment, Development and Sustainability, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Sugarcane-bagasse-ash in enhanced mesophilic Co-digestion for biogas and nutrient recovery: A concept of developing rural circular bioeconomy - Shahid Mumtaz; Yasir Abbas; Iftikhar Ahmad; Ahmed Hassan; Muhammad Farhan Saeed; Sining Yun; Zainab M. Almarhoon; Mohamed Shelkh; Ahmed M. Hassan; P. Rosaiah; Maduru Suneetha; Awais Ahmad (Environmental Research, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Solubilization and Uptake of Phosphorus (P) by Wheat and Maize Crops from Indigenous Rock Phosphate Applied with Biogas Slurry and Bagasse Ash - Ammara Farooq; Bushra Saeed; Hafiz Muhammad Bilal; Muhammad Aamer Maqsood; Muhammad Nasim; Tariq Aziz; Minggang Xu (Water, Air, & Soil Pollution, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Investigating the effects of matrix acidizing and acid fracturing on the production optimization of a carbonate reservoir: a case study - Umair Qureshi; Haris Ahmed Qureshi; Amanat Ali Bhatti; Muhammad Salman Saeed; Muhammad Sameer Khalid (Arabian Journal of Geosciences, 2023)

Glutathione and zinc application upregulate the antioxidant system increasing photosynthetic pigments and growth under water stress in maize (Zea mays L.) - Farah Saeed; Abida Kausar; Qasim Ali; Athar Mahmood; Talha Javed; Rubab Shabbir; Muhammad Fraz Ali (Brazilian Journal of Botany, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Titanium doped cobalt ferrite fabricated graphene oxide nanocomposite for efficient photocatalytic and antibacterial activities - Kiran Khalid; Anam Zahra; Umay Amara; Muhammad Khalid; Muhammad Hanif; Mubashir Aziz; Khalid Mahmood; Muhammad Ajmal; Muhammad Asif; Kinza Saeed; Muhammad Farooq Qayyum; Waseem Abbas (Chemosphere, 2023)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

Unraveling the effects of zinc sulfate nanoparticles and potassium fertilizers on quality of maize and associated health risks in Cd contaminated soils under different moisture regimes - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Rashid Minhas; Abdul Manan Saeed; Muhammad Saqib; Muhammad Aslam (Science of The Total Environment, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Hydrothermal synthesis of V2O5/TiO2 decorated graphitic carbon nitride nanocomposite for biomolecule oxidation inhibition and dye degradation applications - Muhammad Waseem; Awais Ahmad; Muhammad Sagir; Umer Younas; Zohaib Saeed; Muhammad Pervaiz; Faisal Ali; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Rama Rao Karri (Environmental Research, 2023)

“Garlic and ginger extracts mediated green synthesis of silver and gold nanoparticles: A review on recent advancements and prospective applications’’ - Zohaib Saeed; Muhammad Pervaiz; Anam Ejaz; Shah Hussain; Shumila Shaheen; Behram Shehzad; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Enhancing the stability of shale in water-based fluid with polyethylene glycol/nanosilica composite grafted with sodium dodecyl sulfate - Shafeeg Omer Blkoor; Muhammad Noorul Anam Bin Mohd Norddin; Issham Ismail; Jeffrey Onuoma Oseh; Saeed S. Basaleh; Abdul Rahim Bin Risal; Mohd Firdaus Bin Sariman; Eugene N. Ngouangna (Arabian Journal of Geosciences, 2023)

RETRACTED ARTICLE: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2023)

Mucoadhesive (Type-I) and Floating (Type-II) Chitosan Beads for Improved Gastric Retention of Clarithromycin - Habib Ur Rehman; Muhammad Danish Saeed; Faqir Ullah; Faiqa Falak Naz; Kamran Ahmad Khan; Kifayat Ullah Shah (Journal of Pharmaceutical Innovation, 2023)

Wood as a green and sustainable alternative for environmentally friendly & flexible electronic devices - Hizbullah Malik; Muhammad Bilal Khan Niazi; Waheed Miran; Ahmed M. Tawfeek; Zaib Jahan; Emadeldin M. Kamel; Nouman Ahmed; Muhammad Saeed Akhtar (Chemosphere, 2023)

Effects of different fat replacers on functional and rheological properties of low-fat mozzarella cheeses: A review - Aqsa Akhtar; Iqra Nasim; Muhammad Saeed ud Din; Tetsuya Araki; Nauman Khalid (Trends in Food Science & Technology, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Improving bio aviation fuel yield from biogenic carbon sources through electrolysis assisted chemical looping gasification - Mohammad Shahrivar; Muhammad Nauman Saeed; Gajanan Dattarao Surywanshi; Tobias Mattisson; Amir H. Soleimanisalim (Fuel, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Chitosan decorated zirconium metal-organic framework for collaborative adsorption and photocatalytic degradation of methylene blue and methyl orange - Abdul Naeem; Tooba Saeed; Murtaza Sayed; Bashir Ahmad; Tahira Mahmood; Muhammad Farooq; Fouzia Perveen (Process Safety and Environmental Protection, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Improved photocatalytic decolorization of reactive black 5 dye through synthesis of graphene quantum dots–nitrogen-doped TiO2 - Muhammad Saqib Khan; Nadia Riaz; Saeed Rehman; Liu Chenhui; Ahson Jabbar Shaikh; Muhammad Arfan; Iftikhar Zeb; Muhammad Arshad; Farhan Hafeez; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Nickel (Ni) phytotoxicity and detoxification mechanisms: A review - Adnan Mustafa; Usman Zulfiqar; Muhammad Zahid Mumtaz; Maja Radziemska; Fasih Ullah Haider; Jiri Holatko; Tereza Hammershmiedt; Muhammad Naveed; Hassan Ali; Antonin Kintl; Qudsia Saeed; Jiri Kucerik; et al. (Chemosphere, 2023)

Institutional and country level determinants of vertical integration: New evidence from the oil and gas industry - Muhammad Kashif Ali; Muhammad Khurram Zahoor; Asif Saeed; Safia Nosheen; Thanarerk Thanakijsombat (Resources Policy, 2023)

An approach to assess offshore wind power potential using bathymetry and near-hub-height reanalysis data - Zia ul Rehman Tahir; Muhammad Abdullah; Sajeer Ahmad; Ammara Kanwal; Muhammad Farhan; Usama Bin Saeed; Tariq Ali; Imran Amin (Ocean Engineering, 2023)

Synthesis and two-step KOH based activation of porous biochar of wheat straw and waste tire for adsorptive exclusion of chromium (VI) from aqueous solution; thermodynamic and regeneration study - Usama Jamil; Muhammad Zeeshan; Shoaib Raza Khan; Sara Saeed (Journal of Water Process Engineering, 2023)

Distinct climatic regions drive antibiotic resistance genes dynamics across public parks and pristine soil ecosystems - Muhammad Khalid; Xinxin Liu; Bangxiao Zheng; Lantian Su; D. Johan Kotze; Heikki Setälä; Mehran Ali; Asad Rehman; Saeed-ur- Rahman; Nan Hui (Journal of Cleaner Production, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

A causal link between financialization and ecological status: a novel framework for Asian countries? - Saeed Ahmad Sabir; Mubeen Abdur Rehman; Muhammad Zahid Javed; Usman Mehmood; Rabia Ishaq (Environmental Science and Pollution Research, 2023)

Application of micro/nano-fluidics for encapsulation of food bioactive compounds - principles, applications, and challenges - Shahida Anusha Siddiqui; Muhammad Qudrat Ullah Farooqi; Shuva Bhowmik; Zahra Zahra; M.M. Chayan Mahmud; Elham Assadpour; Ren-You Gan; Mohammad Saeed Kharazmi; Seid Mahdi Jafari (Trends in Food Science & Technology, 2023)

Optimum Zinc Fertilization and Sowing Date Improved Growth, Yield Components, and Grain Zn Contents of Bread Wheat Under Different Tillage Systems - Ijaz Hussain; Muhammad Ijaz; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Ahmad Nawaz; Abdul Ghaffar; Muhammad Habib ur Rahman; Saeed Ahmad; Iqra Rasheed; Omaima Nasif; Mohammad Javed Ansari (Journal of Soil Science and Plant Nutrition, 2023)

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Evaluating powder preparation of Dodonaea viscosa as a new potential control measure against bacterial wilt of tomato - Kashif Ahmad; Raja Asad Ali Khan; Musharaf Ahmad; Rizwan Khan; Ishrat Naz; Saeed Ullah; Waleed Khan; Muhammad Waleed; Shahab Khan; Asad Zaman (Journal of Plant Pathology, 2023)

Biocompatible cellulose acetate supported ammonium based ionic liquid membranes; way forward to remediate water pollution - Amina Khalid; Sana Zulfiqar; Noshabah Tabassum; Amir Sada Khan; Muhammad Amin Abid; Muhammad Saeed Akhtar; Fahad Al-Misned; Ahmed Muteb Aljuwayid; Sasan Zahmatkesh; Saira Asif (Chemosphere, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

Glutathione treatment suppresses the adverse effects of microplastics in rice - Fu Chen; Muhammad Aqeel; Noreen Khalid; Muhammad Kashif Irshad; Fozia Farhat; Atia Nazir; Jing Ma; Muhammad Saeed Akhtar; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Ali Noman (Chemosphere, 2023)

Membrane reactor for production of biodiesel from nonedible seed oil of Trachyspermum ammi using heterogenous green nanocatalyst of manganese oxide - Rozina; Mushtaq Ahmad; Muhammad Zafar; Awais Bokhari; Muhammad Saeed Akhtar; Razan A. Alshgari; Abdulnasser Mahmoud Karami; Saira Asif (Chemosphere, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

An Insight into Plant Growth-Promoting Rhizobacteria-Mediated Mitigation of Stresses in Plant - Palakshi Borah; Nirmali Gogoi; Saeed Ahmad Asad; Aparna Jyoti Rabha; Muhammad Farooq (Journal of Plant Growth Regulation, 2023)

Interactive effect of salicylic acid and triacontanol to improve lead stress tolerance in maize (Zea mays L.) - Javed Iqbal; Shagufta Perveen; Abida Parveen; Muhammad Saeed; Sara Zafar; Naeem Iqbal (Arabian Journal of Geosciences, 2023)

A novel three-band macroalgae detection index (TMI) for aquatic environments - Majid Nazeer; Mohammad M. M. Alsahli; Janet Elizabeth Nichol; Jiayi Pan; Weicheng Wu; Muhammad Bilal; Urooj Saeed (International Journal of Remote Sensing, 2023)

Synthesis, characterization and adsorption behavior of modified cellulose nanocrystals towards different cationic dyes - Tariq Aziz; Arshad Farid; Sampath Chinnam; Fazal Haq; Mehwish Kiran; Ab Waheed Wani; Zeid A. Alothman; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Muhammad Saeed Akhtar (Chemosphere, 2023)

Membrane-processed honey samples for pollen characterization with health benefits - Nabila; Mushtaq Ahmad; Ashwaq T. Althobaiti; Wahid Ali; Khansa Masood; Mohamed Fawzy Ramadan; Bisha Chaudhary; Muhammad Zafar; Muhammad Saeed Akhtar; Shazia Sultana; Sasan Zahmatkesh; Tariq Mehmood; et al. (Chemosphere, 2023)

Sustainable energy policy, socio-economic development, and ecological footprint: The economic significance of natural resources, population growth, and industrial development - Huo Jie; Irfan Khan; Majed Alharthi; Muhammad Wasif Zafar; Asif Saeed (Utilities Policy, 2023)

Retraction Note: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2023)

Transmission efficiency of Cotton leaf curl Khokhran virus /Cotton leaf curl Multan betasatellite complex by two whitefly cryptic species in Pakistan - Muhammad Afzal; Shafqat Saeed; Hasan Riaz; Muhammad Ishtiaq; M. Habib ur Rahman (International Journal of Tropical Insect Science, 2023)

The promoters of OsGLP genes exhibited differentially methylated sites under drought and salt stress in rice cultivars - Jazba Anum; Charlotte O’Shea; Karen Skriver; Muhammad Saeed; Muhammad Zeeshan Hyder; Sumaira Farrakh; Tayyaba Yasmin (Euphytica, 2023)

Reproductive and metabolic toxic effects of polystyrene microplastics in adult female Wistar rats: a mechanistic study - Anam Saeed; Muhammad Furqan Akhtar; Ammara Saleem; Bushra Akhtar; Ali Sharif (Environmental Science and Pollution Research, 2023)

Can green finance, green technologies, and environmental policy stringency leverage sustainability in China: evidence from quantile-ARDL estimation - Sahar Afshan; Tanzeela Yaqoob; Muhammad Saeed Meo; Bushra Hamid (Environmental Science and Pollution Research, 2023)

RETRACTED: A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2023)

Development of CuO/CuS/MnO2 ternary nanocomposite for visible light-induced photocatalytic degradation of methylene blue - Muhammad Abdullah; Peter John; Muhammad Naeem Ashiq; Sumaira Manzoor; Muhammad Ishfaq Ghori; Mehar Un Nisa; Abdul Ghafoor Abid; Kashif Younas Butt; Saeed Ahmed (Nanotechnology for Environmental Engineering, 2023)

Characterization of Azadirachta indica synthesized silver nanoparticles and its toxicity against Dusky cotton bug, Oxycarenus hyalinipennis Costa (Hemiptera:Lygaeidae) - Muhammad Javaid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Mirza Abdul Qayyum; Muhammad Arslan Khan (International Journal of Tropical Insect Science, 2023)

A Hematological and Histopathological Study on Diphenhydramine Nasal Nano-gel and Nano-emulgel for the Management of Allergic Rhinitis in Animal Model - Hina Javed; Syed Nisar Hussain Shah; Furqan Muhammad Iqbal; Nida Javed; Benish Saeed (AAPS PharmSciTech, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Transformation of waste seed biomass of Cordia myxa into valuable bioenergy through membrane bioreactor using green nanoparticles of indium oxide - Rozina; Mabkhoot Alsaiari; Mushtaq Ahmad; Muhammad Zafar; Farid A. Harraz; Jari S. Algethami; Biljana Šljukić; Diogo M.F. Santos; Muhammad Saeed Akhtar (Chemosphere, 2023)

Synthesis and characterization of porous reduced graphene oxide based geopolymeric membrane with titanium dioxide coating for forward osmosis application - Kashif Khan; Muhammad Irfan; Noor Ul Amin; Heqing Jiang; Saeed Gul (Chemosphere, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Comparison of pennywort and hyacinth in the development of membraned sediment plant microbial fuel cell for waste treatment - Gull Wareen; Maimona Saeed; Noshin Ilyas; Saira Asif; Muhammad Umair; R.Z. Sayyed; Saleh Alfarraj; Wafa A. Alrasheed; Tahir Hussain Awan (Chemosphere, 2023)

Dietary organic zinc and probiotic alleviate induced Eimeria tenella infection in Japanese quails model of coccidiosis - Kashmala Saeeda; Naila Chand; Najeeb Ullah Khan; Muhammad Saeed; Rifat Ullah Khan (Tropical Animal Health and Production, 2023)

Clinical pharmacokinetics of terbutaline in humans: a systematic review - Khadeeja Sultan; Ammara Zamir; Waseem Ashraf; Imran Imran; Hamid Saeed; Anees ur Rehman; Abdul Majeed; Muhammad Fawad Rasool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

A comparative study of different types of the inversion algorithms for the reservoir characterization of Mehar Block, Pakistan - Nizam Ud Din; Muhammad Kashif; Jamil Khan; Zaheer Hussain; Jose N. Mendez; Wasif Saeed (Arabian Journal of Geosciences, 2023)

Transport infrastructure, economic growth, and transport CO2 emissions nexus: Does green energy consumption in the transport sector matter? - Jiapeng Dai; Rafael Alvarado; Sajid Ali; Zahoor Ahmed; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2023)

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Green synthesis of graphene-based metal nanocomposite for electro and photocatalytic activity; recent advancement and future prospective - Shumila Shaheen; Zohaib Saeed; Awais Ahmad; Muhammad Pervaiz; Umer Younas; Rana Rashad Mahmood Khan; Rafael Luque; Saravanan Rajendran (Chemosphere, 2023)

Cleaner production of biodiesel from novel non-edible seed oil (Carthamus lanatus L.) via highly reactive and recyclable green nano CoWO3@rGO composite in context of green energy adaptation - Mamoona Munir; Muhammad Saeed; Mushtaq Ahmad; Amir Waseem; Mustafa Alsaady; Saira Asif; Anas Ahmed; Mohd Shariq Khan; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Fuel, 2023)

Physically separated soil organic matter pools as indicators of carbon and nitrogen change under long-term fertilization in a Chinese Mollisol - Adnan Mustafa; Qudsia Saeed; Mohammad Tahsin Karimi Nezhad; Sun Nan; Gao Hongjun; Zhu Ping; Muhammad Naveed; Xu Minggang; Avelino Nú nez-Delgado (Environmental Research, 2023)

Salinity mitigates cadmium-induced phytotoxicity in quinoa (Chenopodium quinoa Willd.) by limiting the Cd uptake and improved responses to oxidative stress: implications for phytoremediation - Noman Abdal; Ghulam Abbas; Saeed Ahmad Asad; Ayman A. Ghfar; Ghulam Mustafa Shah; Muhammad Rizwan; Shafaqat Ali; Muhammad Shahbaz (Environmental Geochemistry and Health, 2023)

Myco- and phyco-remediation of polychlorinated biphenyls in the environment: a review - Muhammad Kaleem; Abdul Samad Mumtaz; Muhammad Zaffar Hashmi; Aamer Saeed; Farooq Inam; Rooma Waqar; Amber Jabeen (Environmental Science and Pollution Research, 2022)

Effect of selenium accumulation on foraging behavior of pollinators and seed yield in Trifolium alexandrinum L. - Muhammad Awais Ahmad; Mudssar Ali; Shafqat Saeed; Fahim Nawaz (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Establishing a Green, Lean and Six Sigma implementation model for sustainable construction industry: an analysis of driving forces through ISM-MICMAC approach - Kramat Hussain; Zhen He; Naveed Ahmad; Muzaffar Iqbal; Muhammad Zubair Saeed (Environmental Science and Pollution Research, 2022)

Bentonite binding with mercury(II) ion through promotion of reactive oxygen species derived from manure-based dissolved organic matter - Saeed Rehman; Sayyaf Yousaf; Quanyun Ye; Liu Chenhui; Muhammad Bilal; Ahson Jabbar Shaikh; Muhammad Saqib Khan; Sohail Anjum Shahzad; Pingxiao Wu (Environmental Science and Pollution Research, 2022)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

Foliar spray of silicon nanoparticles improved the growth and minimized cadmium (Cd) in wheat under combined Cd and water-limited stress - Muhammad Adrees; Zahra Saeed Khan; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Arsenic and fluoride co-exposure through drinking water and their impacts on intelligence and oxidative stress among rural school-aged children of Lahore and Kasur districts, Pakistan - Muhammad Saeed; Muhammad Yasir Abdur Rehman; Abida Farooqi; Riffat Naseem Malik (Environmental Geochemistry and Health, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Photosynthetic Efficiency and Antioxidant Defense Potential are Key Players in Inducing Drought Tolerance in Transgenic Tobacco Plants Over-Expressing AVP1 - Hamid Manzoor; Muhammad Shahzad Anjam; Fozia Saeed; Sumaira Rasul; Saira Yousaf; Ayesha Kirn; Muhammad Kamran Qureshi; Zafar Ullah Zafar; Muhammad Ashraf; Habib-ur-Rehman Athar (Journal of Plant Growth Regulation, 2022)

RETRACTED ARTICLE: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2022)

Biochar and organic fertilizer amendments stimulate the dynamics of ammonia oxidizers community in a slightly alkaline soil - Muhammad Khalid; Saeed ur Rahman; Xinxin Liu; Nan Hui (Arabian Journal of Geosciences, 2022)

Molecular level characterization of DOM along a freshwater-to-estuarine coastal gradient in the Florida Everglades - Dennys Leyva; Rudolf Jaffé; Jessica Courson; John S. Kominoski; Muhammad Usman Tariq; Fahad Saeed; Francisco Fernandez-Lima (Aquatic Sciences, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Water quality and health risk assessment of trace elements in surface water at Punjnad Headworks, Punjab, Pakistan - Saima Naz; Borhan Mansouri; Ahmad Manan Mustafa Chatha; Qudrat Ullah; Zain Ul Abadeen; Muhammad Zahoor Khan; Adnan Khan; Saba Saeed; Rayees Ahmad Bhat (Environmental Science and Pollution Research, 2022)

Reverse vaccinology approach for multi-epitope centered vaccine design against delta variant of the SARS-CoV-2 - Khurshid Jalal; Kanwal Khan; Zarrin Basharat; Muhammad Naseer Abbas; Reaz Uddin; Fawad Ali; Saeed Ahmad Khan; Syed Shams ul Hassan (Environmental Science and Pollution Research, 2022)

Adrenergic blocker terazosin potentially suppresses acetaminophen induced-acute liver injury in animal models via CYP2E1 gene - Zoya Hashmat; Iffat Saeed Channa; Muhammad Safdar; Mehmet Ozaslan; Muhammad Saeed; Faisal Siddique; Yasmeen Junejo (Toxicological Research, 2022)

Host plants of Phenacoccus solenopsis (Tinsley) affect parasitism of Aenasius bambawalei (Hayat) - Hamza Younas; Muhammad Razaq; Muhammad Omer Farooq; Rabia Saeed (Phytoparasitica, 2022)

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Arsenic contamination, induced symptoms, and health risk assessment in groundwater of Lahore, Pakistan - Habib Ur Rehman; Saeed Ahmed; Mujeeb Ur Rahman; Muhammad Sajid Mehmood (Environmental Science and Pollution Research, 2022)

Do affluent nations value a clean environment and preserve it? Evaluating the N-shaped environmental Kuznets curve - Fiza Shaheen; Khalid Zaman; Muhammad Saeed Lodhi; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Bacterial Redox Cycling of Manganese in Calcareous Soil Enhances the Nutrients Bioavailability to Wheat - Saba Babar; Ghulam Jilani; Adil Mihoub; Aftab Jamal; Iftikhar Ahmad; Arshad Nawaz Chaudhary; Muhammad Farhan Saeed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2022)

Plant Growth and Fruit Quality Response of Strawberry is Improved After Exogenous Application of 24-Epibrassinolide - Muhammad Moaaz Ali; Raheel Anwar; Aman Ullah Malik; Ahmad Sattar Khan; Saeed Ahmad; Zahoor Hussain; Mahmood Ul Hasan; Mudassar Nasir; Faxing Chen (Journal of Plant Growth Regulation, 2022)

Biocidal activity of green synthesized silver nanoformulation by Azadirachta indica extract a biorational approach against notorious cotton pest whitefly, Bemisia tabaci (Homoptera; Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2022)

Arsenic-induced oxidative stress in Brassica oleracea: Multivariate and literature data analyses of physiological parameters, applied levels and plant organ type - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Samina Khalid; Nasir Masood; Saeed Ahmad Qaisrani; Nabeel Khan Niazi; Camille Dumat (Environmental Geochemistry and Health, 2022)

Interactive effect of glycine, alanine, and calcium nitrate Ca(NO3)2 on wheat (Triticum aestivum L.) under lead (Pb) stress - Shagufta Perveen; Abida Parveen; Muhammad Saeed; Rabia Arshad; Sara Zafar (Environmental Science and Pollution Research, 2022)

Effects of replacement of wheat straw with corn stover-based TMR on growth performance, behavioral characteristics, selected blood metabolites, and nutrient digestibility in Beetal bucks - Faisal Majeed; Saeed Ahmed; Muhammad Afzal Rashid; Muhammad Qamar Shahid; Imran Mohsin (Tropical Animal Health and Production, 2022)

Biorational approach for management of whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae), on cotton crop - Muhammad Iqbal; Muhammad Jalal Arif; Shafqat Saeed; Mansoor ul Hasan; Nazir Javed (International Journal of Tropical Insect Science, 2022)

Asymmetric openness-environment nexus in most open OIC countries: new evidence from quantile-on-quantile (QQ) estimation - Sajid Ali; Zulkornain Yusop; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Measurement of age-dependent radiation ingestion doses due to gross alpha and gross beta exposure from medicinal plants - Muhammad Rafique; Chand Shahzadi; Abdul Jabbar; Mumtaz Khan; Saeed Ur Rahman; Syed Shujahat Hussain Bukhari; Shahab Ahmed Abbasi; Nasar Ahmed (Isotopes in Environmental and Health Studies, 2022)

Development of magnesium oxide@carbon fiber paper composite film for the removal of methyl orange from aqueous phase - Saeed Ahmed; Muhammad Yasir Akram; Ashutosh Kumar; Amit Dhir; Zahid Ali; Sushil Kumar Kansal; Jatinder Kumar Ratan (Nanotechnology for Environmental Engineering, 2022)

Citric Acid (CA)–Modified Biochar Improved Available Phosphorus Concentration and Its Half-Life in a P-Fertilized Calcareous Sandy Soil - Adil Mihoub; Abu El-Eyuoon Abu Zied Amin; Hamid Reza Motaghian; Muhammad Farhan Saeed; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2022)

Competency of groundwater recharge of irrigated cotton field subjacent to sowing methods, plastic mulch, water productivity, and yield under climate change - Muhammad Saeed; Ahsan Maqbool; Muhammad Adnan Ashraf; Muhammad Arshad; Kashif Mehmood; Muhammad Usman; Muhammad Arslan Farid (Environmental Science and Pollution Research, 2022)
Irrigated agriculture is a foremost consumer of water resources to fulfill the demand for food and fiber with an increasing population under climate changes; cotton is no exception. Depleting groundwater recharge and water productivity is critical for the sustainable cotton crop yield peculiarly in the semiarid region. This study investigated the water productivity and cotton yield under six different treatments: three sowing methods, i.e., flat, ridge, and bed planting with and without plastic mulch. Cotton bed planting without mulch showed maximum water productivity (0.24 kg.m −3 ) and the highest cotton yield (1946 kg.ha −1 ). Plastic mulching may reduce water productivity and cotton yield. HYDRUS-1D unsaturated flow model was used to access the groundwater recharge for 150 days under six treatments after model performance evaluation. Maximum cumulative recharge was observed 71 cm for the flat sowing method without plastic mulch. CanESM2 was used to predict climate scenarios for RCP 2.6, 4.5, and 8.5 for the 2050s and 2080s by statistical downscale modeling (SDSM) using historical data from 1975 to 2005 to access future groundwater recharge flux. Average cumulative recharge flux declined 36.53% in 2050 and 22.91% in 2080 compared to 2017 without plastic mulch. Multivariate regression analysis revealed that a maximum 23.78% reduction in groundwater recharge could influence future climate change. Further study may require to understand the remaining influencing factor of depleting groundwater recharge. Findings highlight the significance of climate change and the cotton sowing method while accessing future groundwater resources in irrigated agriculture.

Cytotoxic and anticancer activity of a novel synthesized tet-AuNPs simultaneously activates p53 and inhibits NF-kB signaling in SKBR3 cell line - Muhammad Safdar; Mehmet Ozaslan; Yasmeen Junejo; Iffat Saeed Channa (Toxicology and Environmental Health Sciences, 2022)

Muricazine, a new hydrazine derivative from Ranunculus muricatus L. with antioxidant, lipoxygenase and urease inhibitory activities - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Muhammad Shahid; Mehreen Lateef; Salman Zafar (Natural Product Research, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Assessment of major food crops production-based environmental efficiency in China, India, and Pakistan - Muhammad Shoaib Aslam; Pan Huanxue; Sidra Sohail; Muhammad Tariq Majeed; Saeed ur Rahman; Shoaib Ahmad Anees (Environmental Science and Pollution Research, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

Photocatalysis: an effective tool for photodegradation of dyes—a review - Muhammad Saeed; Majid Muneer; Atta ul Haq; Nadia Akram (Environmental Science and Pollution Research, 2022)

Cyperus iria aqueous-ethanol extract ameliorated hyperglycemia, oxidative stress, and regulated inflammatory cytokines in streptozotocin-induced diabetic rats - Myeda Saeed; Ali Sharif; Saeed Ul Hassan; Bushra Akhtar; Faqir Muhammad; Maryam Malik (Environmental Science and Pollution Research, 2022)

Synthesis and characterization of ZnO decorated reduced graphene oxide (ZnO-rGO) and evaluation of its photocatalytic activity toward photodegradation of methylene blue - Asif Nisar; Muhammad Saeed; Majid Muneer; Muhammad Usman; Iltaf Khan (Environmental Science and Pollution Research, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Muriolide, a novel antioxidant lactone from Ranunculus muricatus - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Mehreen Lateef; Muhammad Shahid; Shehla Akbar; Salman Zafar (Natural Product Research, 2021)

Geological and Geomorphological Characteristics of Hingol National Park (HNP), Balochistan: a Geoheritage Candidate from Southern Pakistan - Muhammad Yaseen; Abbas Ali Naseem; Jawad Ahmad; Afrasiab Khan; Abdullah Khan; Muhammad Alamzeb; Adnan Ahmad; Usman Saeed; Arsalan Ahmad (Geoheritage, 2021)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

Environmental and human iodine and selenium status: lessons from Gilgit-Baltistan, North-East Pakistan - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Alex G. Stewart; Scott D. Young (Environmental Geochemistry and Health, 2021)
Iodine and selenium deficiencies are common worldwide. We assessed the iodine and selenium status of Gilgit-Baltistan, Pakistan. We determined the elemental composition (ICP-MS) of locally grown crops ( n = 281), drinking water ( n = 82), urine ( n = 451) and salt ( n = 76), correcting urinary analytes for hydration (creatinine, specific gravity). We estimated dietary iodine, selenium and salt intake. Median iodine and selenium concentrations were 11.5 (IQR 6.01, 23.2) and 8.81 (IQR 4.03, 27.6) µg/kg in crops and 0.24 (IQR 0.12, 0.72) and 0.27 (IQR 0.11, 0.46) µg/L in water, respectively. Median iodised salt iodine was 4.16 (IQR 2.99, 10.8) mg/kg. Population mean salt intake was 13.0 g/day. Population median urinary iodine (uncorrected 78 µg/L, specific gravity-corrected 83 µg/L) was below WHO guidelines; creatinine-corrected median was 114 µg/L but was unreliable. Daily selenium intake (from urinary selenium concentration) was below the EAR in the majority (46–90%) of individuals. Iodine and selenium concentrations in all crops were low, but no health-related environmental standards exist. Iodine concentration in iodised salt was below WHO-recommended minimum. Estimated population average salt intake was above WHO-recommended daily intake. Locally available food and drinking water together provide an estimated 49% and 72% of EAR for iodine (95 µg/day) and selenium (45 µg/day), respectively. Low environmental and dietary iodine and selenium place Gilgit-Baltistan residents at risk of iodine deficiency disorders despite using iodised salt. Specific gravity correction of urine analysis for hydration is more consistent than using creatinine. Health-relevant environmental standards for iodine and selenium are needed.

Multiple geochemical factors may cause iodine and selenium deficiency in Gilgit-Baltistan, Pakistan - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Scott D. Young (Environmental Geochemistry and Health, 2021)
Deficiencies of the micronutrients iodine and selenium are particularly prevalent where populations consume local agricultural produce grown on soils with low iodine and selenium availability. This study focussed on such an area, Gilgit-Baltistan in Pakistan, through a geochemical survey of iodine and selenium fractionation and speciation in irrigation water and arable soil. Iodine and selenium concentrations in water ranged from 0.01–1.79 µg L −1 to 0.016–2.09 µg L −1 , respectively, which are smaller than levels reported in similar mountainous areas in other parts of the world. Iodate and selenate were the dominant inorganic species in all water samples. Average concentrations of iodine and selenium in soil were 685 µg kg −1 and 209 µg kg −1 , respectively, much lower than global averages of 2600 and 400 µg kg −1 , respectively. The ‘reactive’ fractions (‘soluble’ and ‘adsorbed’) of iodine and selenium accounted for < 7% and < 5% of their total concentrations in soil. More than 90% of reactive iodine was organic; iodide was the main inorganic species. By contrast, 66.9 and 39.7% of ‘soluble’ and ‘adsorbed’ selenium, respectively, were present as organic species; inorganic selenium was mainly selenite. Very low distribution coefficients (kd = adsorbed/soluble; L kg −1 ) for iodine (1.07) and selenium (1.27) suggested minimal buffering of available iodine and selenium against leaching losses and plant uptake. These geochemical characteristics suggest low availability of iodine and selenium in Gilgit-Baltistan, which may be reflected in locally grown crops. However, further investigation is required to ascertain the status of iodine and selenium in the Gilgit-Baltistan food supply and population.

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Integration of Seed Priming and Biochar Application Improves Drought Tolerance in Cowpea - Muhammad Farooq; Leila Romdhane; Abdul Rehman; Amal K. M. Al-Alawi; Walid M. Al-Busaidi; Saeed A. Asad; Dong-Jin Lee (Journal of Plant Growth Regulation, 2021)

Venlafaxine demonstrated anti-arthritic activity possibly through down regulation of TNF-α, IL-6, IL-1β, and COX-2 - Mater Hussen Mahnashi; Zeeshan Jabbar; Alamgeer; Hafiz Muhammad Irfan; Mulazim Hussain Asim; Muhammad Akram; Ahmed Saif; Mohammed Abdulrahman Alshahrani; Mohammed Ali Alshehri; Saeed Ahmed Asiri (Inflammopharmacology, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Urban noise assessment and its nonauditory health effects on the residents of Chiniot and Jhang, Punjab, Pakistan - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Nukshab Zeeshan; Predrag Ilić; Muhammad Imran; Muhammad Farhan Saeed (Environmental Science and Pollution Research, 2021)

Fate of selenium in biofortification of wheat on calcareous soil: an isotopic study - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Scott D. Young (Environmental Geochemistry and Health, 2021)
Selenium (Se) biofortification of staple cereal crops can improve the Se nutritional status of populations. A field trial employing an enriched stable isotope of Se ( 77 Se) was undertaken over three consecutive cropping seasons in a coarse-textured, calcareous soil in Gilgit-Baltistan, Pakistan. The objectives were to (1) assess the feasibility and efficiency of Se biofortification, (2) determine the fate of residual Se, and (3) assess the consequences for dietary Se intake. Isotopically enriched 77 Se ( 77 Se Fert ) was applied, either as selenate or as selenite, at three levels (0, 10, and 20 g ha −1 ) to a wheat crop. Residual 77 Se Fert availability was assessed in subsequent crops of maize and wheat without further 77 Se Fert addition. Loss of 77 Se Fert was c.35% by the first (wheat) harvest, for both selenium species, attributable to the practice of flood irrigation and low adsorption capacity of the soil. No 77 Se Fert was detectable in subsequent maize or wheat crops. The remaining 77 Se Fert in soil was almost entirely organically bound and diminished with time following a reversible (pseudo-)first-order trend. Thus, repeat applications of Se would be required to adequately biofortify grain each year. In contrast to native soil Se, there was no transfer of 77 Se Fert to a recalcitrant form. Grain from control plots would provide only 0.5 µg person −1 day −1 of Se. By contrast, a single application of 20 g ha −1 Se VI could provide c. 47 µg person −1 day −1 Se in wheat, sufficient to avoid deficiency when combined with dietary Se intake from other sources (c. 25 µg day −1 ).

Screening of spring wheat (Triticum aestivum L.) germplasm against drought and heat stress - Muhammad Azher Qureeshi; Fida Hussain; Ijaz Rasool Noorka; Saeed Rauf (Cereal Research Communications, 2021)

Petro-physical evaluation and identifying possible resource plays using the porosity and resistivity logs, Lower Indus Basin, Pakistan - Nizam Ud Din; Zhang Hongbing; Muhammad Kashif; Wasif Saeed (Arabian Journal of Geosciences, 2021)

Switching behaviors toward green brands: evidence from emerging economy - Syed Hasnain Alam Kazmi; Muhammad Saeed Shahbaz; Muhammad Shujaat Mubarik; Junaid Ahmed (Environment, Development and Sustainability, 2021)

Deteriorating Habitats and Conservation Strategies to Repopulate the Endangered Indus River Dolphin (Platanista gangetica minor); a Lesson Learned From the Conservation Practices of the Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Ghulam Nabi; Shahid Ahmad; Richard William McLaughlin; Yujiang Hao; Suliman Khan; Naveed Ahmad; Saeed Ahmad; Muhammad Shoaib Kiani; Yuefeng Wu; Dongming Li (Frontiers in Marine Science, 2021)
The Indus River dolphin (IRD; Platanista gangetica minor ) is an endangered and blind freshwater cetacean, endemic to the Indus River system of Pakistan and India. This review article provides detailed information about the major challenges IRDs are facing, and their possible consequences on the population dynamics of the IRD. Furthermore, we have suggested future conservation strategies for the IRD based on the lesson learned from the conservation of the Yangtze finless porpoise (YFP; Neophocaena asiaeorientalis ), a Critically Endangered freshwater cetacean. The major challenges for IRDs are habitat degradation, habitat fragmentation, and several types of industrial and agricultural pollutants. Worsening climatic changes, illegal fishing, and overfishing are additional threats. The construction of several barrages has fragmented the population into several short segments, some of which are too small for the IRDs to survive. In some segments, the population status of the IRD is unknown. In the remaining populations, genetic inbreeding, water shortage, canal entrapment, and altered ecological environment are potent negative factors for the survival of the IRD. Conservation strategies including fishing bans, translocation, and future research (tagging, periodic health assessments, necropsy and virtopsy, understanding the reproductive biology, and genomics) are possible recommendations. Very serious conservation efforts are needed to save the IRD from decline keeping in view the water shortage, pollution, lack of health assessment studies, and habitat degradation and fragmentation.

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

The nexus of sectoral-based CO2 emissions and fiscal policy instruments in the light of Belt and Road Initiative - Muhammad Waqas Akbar; Peng Yuelan; Adnan Maqbool; Zeenat Zia; Muhammad Saeed (Environmental Science and Pollution Research, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

Biostratigraphic investigation and depositional model of the Late Thanetian Ranikot and the Ypresian Laki formations in the subsurface of the Southern Indus Basin, Pakistan - Hussain Asghar; Muhammad Saleem Mughal; Muhammad Sabir Khan; Saeed Abbas; Muhammad Hanif; Gulfam Hussain; Muhammad Ali; Kazim Ali; Amjad Hussain (Arabian Journal of Geosciences, 2021)

Clove (Syzygium aromaticum) and its phytochemicals in ruminant feed: an updated review - Muhammad Saeed; Muhammad S. Khan; Mahmoud Alagawany; Mayada R. Farag; Othman Alqaisi; Amjad I. Aqib; Muhammad Qumar; Faisal Siddique; Mohamed Fawzy Ramadan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Synthesis, characterization, antimicrobial, antioxidant and computational evaluation of N-acyl-morpholine-4-carbothioamides - Hamid Aziz; Aamer Saeed; Muhammad Aslam Khan; Shakeeb Afridi; Farukh Jabeen (Molecular Diversity, 2021)

Elevated anxiety, hypoactivity, memory deficits, decreases of brain serotonin and 5-HT-1A receptors expression in rats treated with omeprazole - Sadia Basharat Ali; Khalid Mahmood; Raheel Saeed; Tabinda Salman; Muhammad Iqbal Choudhary; Darakhshan Jabeen Haleem (Toxicological Research, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Optimizing Phosphorus Levels in Wheat Grown in a Calcareous Soil with the Use of Adsorption Isotherm Models - Muhammad Farhan Saeed; Aftab Jamal; Dost Muhammad; Ghulam Mustafa Shah; Hafiz Faiq Bakhat; Iftikhar Ahmad; Sajjad Ali; Fahid Ihsan; Jingkuan Wang (Journal of Soil Science and Plant Nutrition, 2021)

Groundwater pumping modeling for the sustainable management of urban water supply in Faisalabad city, Pakistan - Abdul Khaliq; Ahsan Maqbool; Husnain Tansar; Allah Bakhsh; Muhammad Saeed; Muhammad Tariq Sarwar; Wang Hui (Arabian Journal of Geosciences, 2021)

Efficient water allocation strategy to overcoming water inequity crisis for sustainability of agricultural land: a case of Southern Punjab, Pakistan - Ahsan Maqbool; Muhammad Adnan Ashraf; Abdul Khaliq; Wang Hui; Muhammad Saeed (Stochastic Environmental Research and Risk Assessment, 2021)

A review of gas chromatographic techniques for identification of aqueous amine degradation products in carbonated environments - Idris Mohamed Saeed; Shaukat Ali Mazari; Peter Alaba; Brahim Si Ali; Badrul Mohamed Jan; Wan Jeffrey Basirun; Yahaya Muhammad Sani; Sabzoi Nizzamuddin; Nabisab Mujawar Mubarak (Environmental Science and Pollution Research, 2021)

Does the modifying role of institutional quality remains homogeneous in GDP-CO2 emission nexus? New evidence from ARDL approach - Usman Mehmood; Salman Tariq; Zia Ul-Haq; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Enhancement of photocatalytic potential and recoverability of Fe3O4 nanoparticles by decorating over monoclinic zirconia - Idrees Khan; Noor Zada; Ibrahim Khan; Muhammad Sadiq; Khalid Saeed (Journal of Environmental Health Science and Engineering, 2020)

Does globalization and financial sector development affect environmental quality? A panel data investigation for the Middle East and North African countries - Abdul Majid Awan; Muhammad Azam; Imran Ullah Saeed; Baher Bakhtyar (Environmental Science and Pollution Research, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Incorporated maize residues will induce more accumulation of new POC in HF compared with that in LF soils: a comparison of different residue types - Yang Wang; Shuangyi Li; Yingde Xu; Ming Li; Te Shan; Weijun Zhang; Xu Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2020)

Heavy metal contamination and exposure risk assessment via drinking groundwater in Vehari, Pakistan - Sana Khalid; Muhammad Shahid; Natasha; Ali Haidar Shah; Farhan Saeed; Mazhar Ali; Saeed Ahmad Qaisrani; Camille Dumat (Environmental Science and Pollution Research, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Gene expression of thrombomodulin, TNF-α and NF-KB in coronary artery disease patients of Pakistan - Muhammad Rafiq; Afrose Liaquat; Nadia Saeed; Ghassan Umair Shamshad; Sana Mumtaz; Muhammad Jawad Khan (Molecular Biology Reports, 2020)

Bacterial-mediated synthesis of silver nanoparticles and their significant effect against pathogens - Saira Saeed; Atia Iqbal; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2020)

Comparing the potential of stereo aerial photographs, stereo very high-resolution satellite images, and TanDEM-X for estimating forest height - Sami Ullah; Matthias Dees; Pawan Datta; Petra Adler; Tahir Saeed; Muhammad Sadiq Khan; Barbara Koch (International Journal of Remote Sensing, 2020)

Modulation of growth and key physiobiochemical attributes after foliar application of zinc sulphate (ZnSO4) on wheat (Triticum aestivum L.) under cadmium (Cd) stress - Shagufta Perveen; Muhammad Saeed; Abida Parveen; Muhammad Tariq Javed; Sara Zafar; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2020)

Detection and molecular characterization of Clerodendron yellow mosaic virus infecting Volkameria inermis in Pakistan - Afzal Akram; Aqsa Hafeez Khan; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Journal of Plant Pathology, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

2D numerical modeling of two dam-break flood model studies in an urban locality - Sajjad Haider; Umer Saeed; Muhammad Shahid (Arabian Journal of Geosciences, 2020)

Water resources and tourism development in South Asia: an application of dynamic common correlated effect (DCCE) model - Muhammad Saeed Meo; Saeed Ahmad Sabir; Hira Arain; Raima Nazar (Environmental Science and Pollution Research, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Recent developments and comparison of transformation strategies for organic halides to aldehydes and ketones - Muhammad Faisal; Aamer Saeed; Danish Shahzad; Parsa Dar; Fayaz Ali Larik (Molecular Diversity, 2020)

Hazards of nitrogen fertilizers and ways to reduce nitrate accumulation in crop plants - Moddassir Ahmed; Muhammad Rauf; Muhammad Akhtar; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2020)

Gene cloning and characterization of Tk1281, a flap endonuclease 1 from Thermococcus kodakarensis - Hira Muzzamal; Qurat ul Ain; Muhammad Sulaiman Saeed; Naeem Rashid (Folia Microbiologica, 2020)

Evaluating the combination of Metarhizium anisopliae and an enhanced form of diatomaceous earth (Grain-Guard) for the environmentally friendly control of stored grain pests - Nadia Saeed; Waqas Wakil; Muhammad Farooq; Muhammad Shakeel; Muhammad Shahid Arain; Qaiser Shakeel (Environmental Monitoring and Assessment, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Quantitative analysis of lead in cows and buffaloes for health assessment - Wuyi Liu; Naunain Mehmood; Humera Saeed; Muhammad Arshad; Zafar Iqbal Khan; Hira Muqaddas (Environmental Science and Pollution Research, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

Effects of silicon nanoparticles on growth and physiology of wheat in cadmium contaminated soil under different soil moisture levels - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Adrees; Muhammad Farooq Qayyum; Sofia Khalid; Muhammad Zia ur Rehman; Muhammad Aleem Sarwar (Environmental Science and Pollution Research, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

Fluorosis and cognitive development among children (6–14 years of age) in the endemic areas of the world: a review and critical analysis - Muhammad Saeed; Riffat Naseem Malik; Atif Kamal (Environmental Science and Pollution Research, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Role of cotton sticks biochar in immobilization of nickel under induced toxicity condition and growth indices of Trigonella corniculata L. - Uzma Younis; Subhan Danish; Saeed Ahmad Malik; Niaz Ahmed; Tariq Muhammad Munir; Muhammad Khalid Rasheed (Environmental Science and Pollution Research, 2020)

Biological Activities of Artemisinins Beyond Anti-Malarial: a Review - Saeed-ur-Rahman; Muhammad Khalid; Sadaf-Ilyas Kayani; Farooq Jan; Ayaz Ullah; Kexuan Tang (Tropical Plant Biology, 2019)

The Effect of Encapsulation on The Stability of Probiotic Bacteria in Ice Cream and Simulated Gastrointestinal Conditions - Muhammad Afzaal; Farhan Saeed; Muhammad Umair Arshad; Muhammad Tahir Nadeem; Muhammad Saeed; Tabussam Tufail (Probiotics and Antimicrobial Proteins, 2019)

Knockdown of CaHSP60-6 confers enhanced sensitivity to heat stress in pepper (Capsicum annuum L.) - Saeed ul Haq; Abid Khan; Muhammad Ali; Wen-Xian Gai; Huai-Xia Zhang; Qing-Hui Yu; Sheng-Bao Yang; Ai-Min Wei; Zhen-Hui Gong (Planta, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Potential nutraceutical and food additive properties and risks of coffee: a comprehensive overview - Muhammad Saeed; Muhammad Naveed; Jannat BiBi; Asghar Ali Kamboh; Lucas Phil; Sun Chao (Critical Reviews in Food Science and Nutrition, 2019)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Knockdown of the chitin-binding protein family gene CaChiIV1 increased sensitivity to Phytophthora capsici and drought stress in pepper plants - Muhammad Ali; Wen-Xian Gai; Abdul Mateen Khattak; Abid Khan; Saeed Ul Haq; Xiao Ma; Ai-Min Wei; Izhar Muhammad; Ibadullah Jan; Zhen-Hui Gong (Molecular Genetics and Genomics, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Nexus of FDI, population, energy production, and water resources in South Asia: a fresh insight from dynamic common correlated effects (DCCE) - Hira Arain; Liyan Han; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2019)

Dynamics of maize straw–derived nitrogen in soil aggregates as affected by fertilization - Yang Wang; Ming Li; Jiubo Pei; Tingting An; Muhammad Farhan Saeed; Te Shan; Yingde Xu; Jingkuan Wang (Journal of Soils and Sediments, 2019)

The accumulation of cadmium in wheat (Triticum aestivum) as influenced by zinc oxide nanoparticles and soil moisture conditions - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Rizwan Javed; Muhammad Adrees (Environmental Science and Pollution Research, 2019)

Development of Whey Protein Concentrate-Pectin-Alginate Based Delivery System to Improve Survival of B. longum BL-05 in Simulated Gastrointestinal Conditions - Iqra Yasmin; Muhammad Saeed; Imran Pasha; Muhammad Anjum Zia (Probiotics and Antimicrobial Proteins, 2019)

Heavy metal exposure through artificial diet reduces growth and survival of Spodoptera litura (Lepidoptera: Noctuidae) - Sajjad Ali; Muhammad Irfan Ullah; Muhammad Farhan Saeed; Samina Khalid; Muhammad Saqib; Muhammad Arshad; Muhammad Afzal; Christos A. Damalas (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

Cysteine-induced alterations in physicochemical parameters of oat ( Avena sativa L. var. Scott and F-411) under drought stress - Shagufta Perveen; Muhammad Iqbal; Muhammad Saeed; Naeem Iqbal; Sara Zafar; Tehmina Mumtaz (Biologia Futura, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

Manganese dioxide nanoparticles/activated carbon composite as efficient UV and visible-light photocatalyst - Idrees Khan; Muhammad Sadiq; Ibrahim Khan; Khalid Saeed (Environmental Science and Pollution Research, 2019)

Copy number profiling of Oncotype DX genes reveals association with survival of breast cancer patients - Washaakh Ahmed; Muhammad Faraz Arshad Malik; Muhammad Saeed; Farhan Haq (Molecular Biology Reports, 2018)

Yucca schidigera can mitigate ammonia emissions from manure and promote poultry health and production - Muhammad Saeed; Muhammad Asif Arain; Muhammad Naveed; Mahmoud Alagawany; Mohamed Ezzat Abd El-Hack; Zohaib Ahmed Bhutto; Marek Bednarczyk; Mohib Ullah Kakar; Mervat Abdel-Latif; Sun Chao (Environmental Science and Pollution Research, 2018)

Carbon fiber paper@MgO films: in situ fabrication and high-performance removal capacity for phosphate anions - Saeed Ahmed; Muhammad Naeem Ashiq; Dianqing Li; Pinggui Tang; Yongjun Feng (Environmental Science and Pollution Research, 2018)

Role of foliar application of sulfur-containing compounds on maize (Zea mays L. var. Malka and hybrid DTC) under salt stress - Shagufta Perveen; Naeem Iqbal; Muhammad Saeed; Sara Zafar; Zunaira Arshad (Brazilian Journal of Botany, 2018)

Role of sorption energy and chemisorption in batch methylene blue and Cu2+ adsorption by novel thuja cone carbon in binary component system: linear and nonlinear modeling - Saeed Rehman; Adnan Adil; Ahsan Jabbar Shaikh; Jehanzeb Ali Shah; Muhammad Arshad; Muhammad Arif Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Yield Forecasting of Spring Maize Using Remote Sensing and Crop Modeling in Faisalabad-Punjab Pakistan - Ishfaq Ahmad; Umer Saeed; Muhammad Fahad; Asmat Ullah; M. Habib ur Rahman; Ashfaq Ahmad; Jasmeet Judge (Journal of the Indian Society of Remote Sensing, 2018)

Classification of rocks radionuclide data using machine learning techniques - Abdul Razzaq Khan; Adil Aslam Mir; Sharjil Saeed; Muhammad Rafique; Khawaja M. Asim; Talat Iqbal; Abdul Jabbar; Saeed Ur Rahman (Acta Geophysica, 2018)

Impact of soil salinity on the microbial structure of halophyte rhizosphere microbiome - Salma Mukhtar; Babur Saeed Mirza; Samina Mehnaz; Muhammad Sajjad Mirza; Joan Mclean; Kauser Abdulla Malik (World Journal of Microbiology and Biotechnology, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Introgression and inheritance of charcoal rot (Macrophomina phaseolina) resistance from silver sunflower (Helianthus argophyllus Torr. & A. Gray) into cultivated sunflower (Helianthus annuus L.) - Muhammad Shehbaz; Saeed Rauf; Abdullah M. Al-Sadi; Shahid Nazir; Saira Bano; M. Shahzad; Muhammad Mubashar Hussain (Australasian Plant Pathology, 2018)

A comparative study to evaluate efficiency of EDTA and calcium in alleviating arsenic toxicity to germinating and young Vicia faba L. seedlings - Marina Rafiq; Muhammad Shahid; Saliha Shamshad; Sana Khalid; Nabeel Khan Niazi; Ghulam Abbas; Muhammad Farhan Saeed; Mazhar Ali; Behzad Murtaza (Journal of Soils and Sediments, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Effectiveness of an improved form of insecticide-based diatomaceous earth against four stored grain pests on different grain commodities - Nadia Saeed; Muhammad Farooq; Muhammad Shakeel; Misbah Ashraf (Environmental Science and Pollution Research, 2018)

Cucurmin, anticancer, & antitumor perspectives: A comprehensive review - Muhammad Imran; Azmat Ullah; Farhan Saeed; Muhammad Nadeem; Muhammad Umair Arshad; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Nucleosomes positioning around transcriptional start site of tumor suppressor (Rbl2/p130) gene in breast cancer - Farman Ullah Farman; Mehwish Iqbal; Muhammad Azam; Muhammad Saeed (Molecular Biology Reports, 2018)

Determination and estimation of magnesium content in the single phase magnesium-calcite [Ca(1−x)MgxCO3(s)] using electron probe micro-analysis (EPMA) and X-ray diffraction (XRD) - Muhammad Fahad; Sundas Saeed (Geosciences Journal, 2018)

Augmentation with potential endophytes enhances phytostabilization of Cr in contaminated soil - Muhammad T. Ahsan; Muhammad Najam-ul-haq; Abdul Saeed; Tanveer Mustafa; Muhammad Afzal (Environmental Science and Pollution Research, 2018)

Ag@MnxOy: an effective catalyst for photo-degradation of rhodamine B dye - Muhammad Saeed; Aziz Ahmad; Rajender Boddula; Inamuddin; Atta ul Haq; Aisha Azhar (Environmental Chemistry Letters, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Presence of less-preferred hosts of the aphid parasitoids Aphidius ervi and Praon volucre reduces parasitism efficiency - Muhammad Mubashir Saeed; Abu Bakar Muhammad Raza; Muhammad Afzal; Anjum Aqueel; Muhammad Farooq; Thierry Hance (Phytoparasitica, 2018)

Remarks on genetic diversity and relationship of Punica protopunica and P. granatum assessed by molecular analyses - Muhammad Youssef; Arif Saeed Alhammadi; Jorge Humberto Ramírez-Prado; Lorenzo Felipe Sánchez-Teyer; Rosa María Escobedo-GraciaMedrano (Genetic Resources and Crop Evolution, 2018)

Correction to: HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Muhammad Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

Excessive use of nitrogenous fertilizers: an unawareness causing serious threats to environment and human health - Moddassir Ahmed; Muhammad Rauf; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2017)

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests - Misbah Ashraf; Muhammad Farooq; Muhammad Shakeel; Naima Din; Shahbaz Hussain; Nadia Saeed; Qaiser Shakeel; Nasir Ahmed Rajput (Environmental Science and Pollution Research, 2017)

Reconsidering betaine as a natural anti-heat stress agent in poultry industry: a review - Muhammad Saeed; Daryoush Babazadeh; Muhammad Naveed; Muhammad Asif Arain; Faiz Ul Hassan; Sun Chao (Tropical Animal Health and Production, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Essential oils of aromatic Egyptian plants repel nymphs of the tick Ixodes ricinus (Acari: Ixodidae) - Hesham R. El-Seedi; Muhammad Azeem; Nasr S. Khalil; Hanem H. Sakr; Shaden A. M. Khalifa; Khalijah Awang; Aamer Saeed; Mohamed A. Farag; Mohamed F. AlAjmi; Katinka Pålsson; Anna-Karin Borg-Karlson (Experimental and Applied Acarology, 2017)

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

Synthesis, computational studies and biological evaluation of new 1-acetyl-3-aryl thiourea derivatives as potent cholinesterase inhibitors - Aamer Saeed; Muhammad Shakil Shah; Fayaz Ali Larik; Shafi Ullah Khan; Pervaiz Ali Channar; Ulrich Flörke; Jamshed Iqbal (Medicinal Chemistry Research, 2017)

Seed health of organic peas and faba beans and its effects on the health of the harvested grains - Muhammad Farhan Saeed; Jelena Baćanović; Christian Bruns; Harald Schmidt; Maria Renate Finckh (Journal of Plant Diseases and Protection, 2017)

Terbufos sulfone aggravates kidney damage in STZ-induced diabetic rats - Syed Muhammad Nurulain; Shreesh Ojha; Mohamed Shafiullah; Javed Yasin; Tayyaba Yasmin; Tariq Saeed; Ernest Adeghate (Biologia, 2017)

Effect of Rheology and Poloxamers Properties on Release of Drugs from Silicon Dioxide Gel-Filled Hard Gelatin Capsules—A Further Enhancement of Viability of Liquid Semisolid Matrix Technology - Misbah Sultana; Mobashar Ahmad Butt; Tariq Saeed; Rizwan Mahmood; Saeed ul Hassan; Khalid Hussain; Syed Atif Raza; Muhammad Ahsan; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Manganese nutrition improves the productivity and grain biofortification of fine grain aromatic rice in conventional and conservation production systems - Aman Ullah; Muhammad Farooq; Asif Nadeem; Abdul Rehman; Saeed A. Asad; Ahmad Nawaz (Paddy and Water Environment, 2017)

A new glycosidic antioxidant from Ranunculus muricatus L. (Ranunculaceae) exhibited lipoxygenasae and xanthine oxidase inhibition properties - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Shahid; Mehreen Lateef (Natural Product Research, 2017)

Single and Combined Impacts of Vitamin A and Selenium in Diet on Productive Performance, Egg Quality, and Some Blood Parameters of Laying Hens During Hot Season - Mohamed E. Abd El-Hack; Khalid Mahrose; Ali A. Askar; Mahmoud Alagawany; Muhammad Arif; Muhammad Saeed; Farzana Abbasi; Rab Nawaz Soomro; Farman Ali Siyal; Maria Tabassum Chaudhry (Biological Trace Element Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

Transgenic expression of phytase in wheat endosperm increases bioavailability of iron and zinc in grains - Nabeela Abid; Asia Khatoon; Asma Maqbool; Muhammad Irfan; Aftab Bashir; Irsa Asif; Muhammad Shahid; Asma Saeed; Henrik Brinch-Pedersen; Kauser A. Malik (Transgenic Research, 2017)

Multichromic Bis-Axially Extended Perylene Chromophore with Schiff Bases: Synthesis, Characterization and Electrochemical Studies - Ghulam Shabir; Aamer Saeed; Muhammad Arshad; Muhammad Zahid (Journal of Fluorescence, 2016)

Biochar enhances the cadmium tolerance in spinach (Spinacia oleracea) through modification of Cd uptake and physiological and biochemical attributes - Uzma Younis; Saeed Ahmad Malik; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Hasnain Raza Shah; Rabia Abdur Rehman; Niaz Ahmad (Environmental Science and Pollution Research, 2016)

The 35-amino acid C2 protein of Cotton leaf curl Kokhran virus, Burewala, implicated in resistance breaking in cotton, retains some activities of the full-length protein - Fazal Akbar; Zafar Iqbal; Rob W. Briddon; Franck Vazquez; Muhammad Saeed (Virus Genes, 2016)

Piroxicam sulfonates biology-oriented drug synthesis (BIODS), characterization and anti-nociceptive screening - Safi Ullah; Muhammad Saeed; Syed Muhammad Ashhad Halimi; Muhammad Imran Fakhri; Khalid Mohammed Khan; Ikhtiar Khan; Shahnaz Perveen (Medicinal Chemistry Research, 2016)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

Quantitative trait locus mapping for salt tolerance at maturity stage in indica rice using replicated F2 population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2016)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

A Novel Approach Based on Data Redundancy for Feature Extraction of EEG Signals - Hafeez Ullah Amin; Aamir Saeed Malik; Nidal Kamel; Muhammad Hussain (Brain Topography, 2016)

Wheat Allergy and Intolerence; Recent Updates and Perspectives - Imran Pasha; Farhan Saeed; Muhammad Tauseef Sultan; Rizwana Batool; Mahwash Aziz; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2016)

In vitro anti-oxidant potential of new metabolites from Hypericum oblongifolium (Guttiferae) - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Imran Ali (Natural Product Research, 2015)

Le4 Is an Epicotyl Preferential Homologue of the Soybean Seed-Specific Le1 Lectin and the Vegetative Le3 Lectin Genes - Muhammad Chragh; Yevgen Zolotarov; Hanaa Saeed; Martina V. Strömvik (Plant Molecular Biology Reporter, 2015)

Study of physio-psychological effects on traffic wardens due to traffic noise pollution; exposure-effect relation - Shamas Tabraiz; Saeed Ahmad; Iffat Shehzadi; Muhammad Bilal Asif (Journal of Environmental Health Science and Engineering, 2015)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

Synthesis, characterization and theoretical calculations of (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride complexes: in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; Muhammad Altaf; Abdulaziz A. Al-Saadi; Abdel-Nasser Kawde; Saleh Altuwaijri; Saeed Ahmad; Anvarhusein A. Isab (BioMetals, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

The importance of alternative host plants as reservoirs of the cotton leaf hopper, Amrasca devastans, and its natural enemies - Rabia Saeed; Muhammad Razaq; Ian C. W. Hardy (Journal of Pest Science, 2015)

Identification of quantitative trait loci for Na+, K+ and Ca++ accumulation traits in rice grown under saline conditions using F2 mapping population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2015)

Optical, Electrochemical and Thermoanalytical Investigations on Newly-Synthesized Perylene-3,4,9,10-Dianhydride Fluorescent Dyes - Aamer Saeed; Ghulam Shabir; Muhammad Arshad (Journal of Fluorescence, 2015)

Impact of rapid urbanization on microclimate of urban areas of Pakistan - Adnan Ahmad Tahir; Adnan Muhammad; Qaisar Mahmood; Sheikh Saeed Ahmad; Zahid Ullah (Air Quality, Atmosphere & Health, 2015)

Three gene products of a begomovirus–betasatellite complex restore expression of a transcriptionally silenced green fluorescent protein transgene in Nicotiana benthamiana - Muhammad Saeed; Gabi Krczal; Michael Wassenegger (Virus Genes, 2015)

Protein–Energy Malnutrition: A Risk Factor for Various Ailments - Rizwana Batool; Masood Sadiq Butt; Muhammad Tauseef Sultan; Farhan Saeed; Rabia Naz (Critical Reviews in Food Science and Nutrition, 2015)

Onion: Nature Protection Against Physiological Threats - Hafiz Ansar Rasul Suleria; Masood Sadiq Butt; Faqir Muhammad Anjum; Farhan Saeed; Nauman Khalid (Critical Reviews in Food Science and Nutrition, 2015)

Anthocyanin production in the hyperaccumulator plant Noccaea caerulescens in response to herbivory and zinc stress - Saeed Ahmad Asad; Said Muhammad; Muhammad Farooq; Aftab Afzal; Martin Broadley; Scott Young; Helen West (Acta Physiologiae Plantarum, 2015)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

Determinants of farmers’ choice of coping and adaptation measures to the drought hazard in northwest Balochistan, Pakistan - Muhammad Ashraf; Jayant K. Routray; Muhammad Saeed (Natural Hazards, 2014)

Pharmacological importance of an ethnobotanical plant: Capsicum annuum L. - Farhan A. Khan; Tariq Mahmood; Muhammad Ali; Abdul Saeed; Aneela Maalik (Natural Product Research, 2014)

An analysis of the resistance of Gossypium arboreum to cotton leaf curl disease by grafting - Rahim Ullah; Khalid P. Akhtar; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2014)

An efficient total synthesis of trilepisiumic acid - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Total synthesis of cytotoxic metabolite ( ± )-desmethyldiaportinol from Ampelomyces sp. - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Synthesis and biological evaluation of some N 4-aryl-substituted 5-fluoroisatin-3-thiosemicarbazones - Humayun Pervez; Naveeda Saira; Mohammad Saeed Iqbal; Muhammad Yaqub; Khalid Mohammed Khan (Medicinal Chemistry Research, 2013)

Drug interactions and synthesis of cefpirome with hypoglycemic agents - Muhammad Nawaz; Muhammad Saeed Arayne; Najma Sultana (Medicinal Chemistry Research, 2013)

Two new triterpenes from Alstonia scholaris flowers - Nighat Sultana; Zafar Saeed Saify; Muhammad Saleem; Mustafa Kamal (Natural Product Research, 2013)

Isolation of long-chain esters from the rhizome of Polygonatum verticillatum by potent tyrosinase inhibition - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Izhar-ul-Haq; Naveed Muhammad; Rukhsana Ghaffar (Medicinal Chemistry Research, 2013)

Synthesis, spectroscopic, and biological evaluation of some levofloxacin metal complexes - Najma Sultana; Muhammad Saeed Arayne; Syeda Bushra Shakeb Rizvi; Urooj Haroon; Muhammad Ahmed Mesaik (Medicinal Chemistry Research, 2013)

Flow injection online spectrophotometric determination of uranium after preconcentration on XAD-4 resin impregnated with nalidixic acid - Shabnam Shahida; Akbar Ali; Muhammad Haleem Khan; Muhammad Mufazzal Saeed (Environmental Monitoring and Assessment, 2013)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Nutraceutical and Functional Scenario of Wheat Straw - Imran Pasha; Farhan Saeed; Khalid Waqas; Faqir Muhammad Anjum; Muhammad Umair Arshad (Critical Reviews in Food Science and Nutrition, 2013)

Evaluation of n-hexane extract of Viola betonicifolia for its neuropharmacological properties - Naveed Muhammad; Muhammad Saeed; Haroon Khan; Ikramul Haq (Journal of Natural Medicines, 2013)

Rb1/105 gene alterations and head and neck carcinogenesis - Maimoona Sabir; Ruqia Mehmood Baig; Ishrat Mahjabeen; Muhammad Saeed; Faraz Arshad Malik; Mahmood Akhtar Kayani (Molecular Biology Reports, 2012)

Biomass partitioning and genetic analyses of salinity tolerance in sunflower (Helianthus annuus L.) - Saeed Rauf; Muhammad Shahzad; Jaime A. Teixeira da Silva; Ijaz Rasool Noorka (Journal of Crop Science and Biotechnology, 2012)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

Environmental impact assessment (EIA): an overlooked instrument for sustainable development in Pakistan - Rashid Saeed; Ayesha Sattar; Zafar Iqbal; Muhammad Imran; Raziya Nadeem (Environmental Monitoring and Assessment, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

Effect of Mineral Fortification on Plasma Biochemical Profile in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; Munammad Tauseef Sultan; Muhammad Riaz; Anwaar Ahmed (Biological Trace Element Research, 2011)

Liquid chromatographic analysis of halofantrine from dosage form and its metal interaction studies - Najma Sultana; Muhammad Saeed Arayne; Muhammad Nawaz; Zia Ur Rehman (Medicinal Chemistry Research, 2011)

Arabinoxylans and Arabinogalactans: A Comprehensive Treatise - Farhan Saeed; Imran Pasha; Faqir Muhammad Anjum; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2011)

Oxidative stress elevated DNA damage and homocysteine level in normal pregnant women in a segment of Pakistani population - Shazia A. Bukhari; Muhammad Ibrahim Rajoka; Z. Ibrahim; Fatima Jalal; Shahid Mahboob Rana; Saeed A. Nagra (Molecular Biology Reports, 2011)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Development and Evaluation of Hydrophilic Colloid Matrix of Famotidine Tablets - Muhammad Harris Shoaib; Saniah Al Sabah Siddiqi; Rabia Ismail Yousuf; Kamran Zaheer; Muhammad Hanif; Saeed Rehana; Sabahat Jabeen (AAPS PharmSciTech, 2010)

Comparative efficacy of surface drying and re-drying seed priming in rice: changes in emergence, seedling growth and associated metabolic events - Muhammad Farooq; Abdul Wahid; Nazir Ahmad; Saeed A. Asad (Paddy and Water Environment, 2010)

Plasma homocysteine and DNA damage profiles in normal and obese subjects in the Pakistani population - Shazia A. Bukhari; Muhammad I. Rajoka; Saeed A. Nagra; Zia Ur Rehman (Molecular Biology Reports, 2010)

Coexistence of arbuscular mycorrhizae and dark septate endophytic fungi in an undisturbed and a disturbed site of an arid ecosystem - Muhammad S. Chaudhry; Syed U. Rahman; Muhammad S. Ismaiel; Ghulam Sarwar; Bushra Saeed; Faiz-ul-Hassan Nasim (Symbiosis, 2009)

Leishmanicidal potential of N-substituted morpholine derivatives: Synthesis and structure–activity relationships - Khalid Mohammed Khan; Muhammad Zarrar Khan; Muhammad Taha; Ghulam Murtaza Maharvi; Zafar Saeed Saify; Shahnaz Parveen; Muhammad Iqbal Choudhary (Natural Product Research, 2009)

Limitations observed in the use of agroinoculation for geminivirus research - Muhammad Saeed (Virus Genes, 2008)

Comparison of conventional puddling and dry tillage in rice–wheat system - Muhammad Farooq; Shahzad M. A. Basra; Saeed A. Asad (Paddy and Water Environment, 2008)

Pharmacokinetic Study of Copper (II) Acetylsalicylate - Mohammad S. Iqbal; Muhammad Sher; Humayun Pervez; Maryiam Saeed (Biological Trace Element Research, 2008)

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke - Sheikh Arshad Saeed; Kaneez Fatima Shad; Taimur Saleem; Faisal Javed; Muhammad Umair Khan (Experimental Brain Research, 2007)

Immobilization of blue green microalgae on loofa sponge to biosorb cadmium in repeated shake flask batch and continuous flow fixed bed column reactor system - Asma Saeed; Muhammad Iqbal (World Journal of Microbiology and Biotechnology, 2006)

New insight in staphylococcin research: bacteriocin and/or bacteriocin-like inhibitory substance(s) produced by S. aureus AB188 - Sadia Saeed; Sheikh Ajaz Rasool; Samia Ahmed; Tanweer Khanum; Muhammad Bashir Khan; Atiya Abbasi; Syed Abid Ali (World Journal of Microbiology and Biotechnology, 2006)